Phthalate esters and microplastics in sediments of Haomeiliao Wetland, Southwestern Taiwan: Occurrence, spatial distribution, and management implications - Aila Marie Bandola; Ming-Huang Wang; Bo-Fu Guo; Kristopher Ray S. Pamintuan; Chiu-Wen Chen; Cheng-Di Dong (Marine Pollution Bulletin, 2026)

Experimental study and soft computing modeling of shaly oil and gas reservoir cation exchange capacity based on novel machine learning approach - Wu Xiaobin; Zyad Shaaban; R. Roopashree; Anupam Yadav; Subhashree Ray; Chandra Kant Bhardwaj; Aashna Sinha; Dilsora Abduvalieva; Prakhar Tomar; Heyder Mhohamdi; Usama S. Altimari; Aseel Smerat; et al. (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Evaluating CCN activity through size-resolved hygroscopicity: Synergistic observations and simulations in a tropical montane region - Avishek Ray; G. Pandithurai; Bipin Kumar; S. Mukherjee; Lois Thomas; V. Anil Kumar; Rohit D. Patil (Atmospheric Environment, 2026)

A Hirota three-soliton obstruction for a complex-order KdV-type bilinear family - S. Ray (Wave Motion, 2026)

Revisit of hydrothermal plumes along 63°- 64°E of Carlsberg Ridge: A comprehensive survey to assess physicochemical features of non-buoyant plumes - Lina L. Fernandes; Durbar Ray; S. Gautham; V.P. Akhil; Robin John; V. Yatheesh (Journal of Marine Systems, 2026)

Impact of iron and zinc fortification on whole wheat flour properties, chapatti quality, storage stability and mineral bioaccessibility - M S Ashwin Kumar; Amrita Ray; A Jyothi Lakshmi; Suresh D. Sakhare (Food Chemistry, 2026)

Regional bio‐mobility of bovines during the Harappan period: Evidence from stable C–O–Sr isotopes of faunal bioapatite at Kanmer and Tigrana - Milan K. Mahala; Amzad H. Laskar; Pankaj Goyal; Jeewan S. Kharakwal; Narender Parmar; Yadubir S. Rawat; Angad Lamba; Alok K. Kanungo; Jyotiranjan S. Ray (Journal of Quaternary Science, 2026)
Studies on biomobility in the Indus Valley Civilisation (IVC) or the Harappan Culture provide important insights into pastoral practices, trade and environmental adaptation that shaped the civilisation's economy and social networks. At its height, the IVC engaged in extensive trade across its vast territory, resulting in cultural and economic change across diverse ecological zones. Although archaeological finds indicate trade in artefacts throughout the civilisation, our understanding of human and animal mobility remains limited due to a lack of geochemical and isotopic data on provenance. A key unresolved issue in biomobility is distinguishing between local and broader animal husbandry practices and their trade connections. To address this, we analysed faunal teeth, bone bioapatite and bone‐encased soil using C–O–Sr–Nd isotopes from two Harappan sites, Kanmer (Gujarat) and Tigrana (Haryana), located more than 900 km apart. Our isotope data and the existing literature suggest that, in Kanmer, specialised animal‐feeding methods were used, and local rainfall was the primary water source across all settlements. Data from both sites show that most sheep/goat were raised locally with little movement; however, bovines in Kanmer from the mature and late‐mature phases had diverse, possibly non‐local origins, likely from Haryana. At Tigrana, some animals also showed signs of movement from nearby regions. Regional movement of bovines from a better watered region to a semi‐arid region may indicate trading as an important aspect of this civilisation embedded within broader social and economic networks.

Little difference in the carbon balance of ryegrass/white clover- and plantain-dominated swards under dairy grazing - A. M. Wall; D. I. Campbell; S. Ray; J. P. Goodrich; L. A. Schipper (Nutrient Cycling in Agroecosystems, 2026)
Incorporating plantain into grazed pasture swards is proposed as an approach to reduce nitrate leaching and nitrous oxide emissions. However, consideration must be given to potential emission-swapping, such as a reduction in soil carbon (C), which can contribute to increases in atmospheric CO 2 . We compared the net ecosystem C balance (NECB) of two adjacent newly-sown paddocks (~ 3 ha each) of (i) traditional ryegrass and white clover pasture (RyWC) and (ii) a pure plantain sward, to assess whether plantain was beneficial or detrimental for the carbon balance. The NECB was calculated by combining eddy covariance (EC) measurements of CO 2 with measurements and estimates of lateral C transfers. Concurrently, regular measurements of sward composition and properties were taken. During the approximately 2.5-year experiment, the RyWC sward had an NECB of −199 g C m −2 period −1 compared with −273 g C m −2 period −1 for the plantain sward. The slightly larger loss from the plantain sward was attributed to lower excretal C returns due to differences in grazing duration (13.9 days for the RyWC paddock, and 5.9 days for the plantain paddock) during the first year of grazing. In the second year, the grazing management of the two paddocks was the same, and the NECBs were comparable. Both pasture dry matter production and CO 2 uptake were similar between the swards, although the lower C content of the plantain resulted in smaller C exports by either harvest or grazing. We conclude that small differences in NECB (and assumed soil C) between a pure plantain sward and a traditional ryegrass and white clover sward are associated with management rather than pasture species.

Matriptase proteolysis selectively drives disassembly and internalization of the claudin-7 complex while preserving E-cadherin - Yu-Ling A. Kao; He-Yu Huang; Yin S. Yu; Nanxi Huang; Ya-Chin Chan; Chen-Ray Lee; Michael D. Johnson; Chen-Yong Lin (Human Cell, 2026)

Hybridized Time Series Modeling with Machine Learning Techniques for Pomegranate Price Fluctuations - S. Vishnu Shankar; Rajeev Ranjan Kumar; Mrinmoy Ray; V. Lavanya; R. Subash (Agricultural Research, 2026)

Antimicrobial and antibiofilm potential of Shorea robusta-derived nanoparticles for topical therapeutic use - Shuaib Burgee; V. Barghavi; Neha Maurya; Swati Bhati; Tulip Biswas; Sumit Sinha-Ray; S Shankara Narayanan; Soumi Sadhu (Biocatalysis and Agricultural Biotechnology, 2026)

Rainfall Dynamics in Sri Lanka Over Five Decades (1970–2023): Implications for Agricultural Adaptation to Climate Change - N. S. Abeysingha; S. D. Madurapperuma Arachchige; M. S. V. Pathirana; Ram L. Ray (International Journal of Climatology, 2026)
Climate change is affecting agricultural productivity and economic stability across many parts of the world, but small islands like Sri Lanka are more vulnerable to the effects of climate change. As a result, assessing recent rainfall dynamics is crucial for developing effective climate adaptation measures. This study analysed rainfall data from 44 meteorological stations across Sri Lanka's dry, wet and intermediate climatic zones spanning 54 years (1970–2023) to evaluate rainfall dynamics. The analysis employed multiple statistical methods, including the coefficient of variation (CV), Precipitation Concentration Index (PCI), Standardized Precipitation Index (SPI), Mann–Kendall (MK) test with Sen's slope estimator and innovative trend analysis (ITA). Results revealed increasing annual rainfall trends at 79.5% of stations, with 40% showing statistically significant increases ( p p

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

CRISP-PTG-Assembler Ver. 1.0: a primer design tool for polycistronic tRNA-gRNA (PTG) assembly for Cas9-based multiplex genome editing in plants - Soham Ray; Joshitha Vijayan; S. Vanchinathan; Rajkumar Dhakar; Nazima Nasrullah; Shivani Nagar; Tushar Kanti Dutta; Viswanthan Chinnusamy (Planta, 2026)

Biochemical and SSR marker-based insights into rice defense mechanisms against Pyricularia oryzae - Joyanti Ray; Mst. Sabiha Sultana; Md. Yasin Ali; S. M. Abdullah Al Mamun; Md. Rezve (Cereal Research Communications, 2026)

Is cinchona (Cinchona sp.) a sustainable land use practice in the Eastern Himalayas of India? A comparative study with other land uses in relation to soil properties and carbon indices - S. K. Reza; Ruma Das; K. M. Hati; S. Chattaraj; A. Daripa; Sreyasi Talukdar; F. H. Rahman; S. K. Ray (Environmental Sustainability, 2026)

The macromolecules and lipid biomarkers as seen in the archean white mfolozi banded iron formation (BIF): Their biogenicity and possible implications for mars - D. Ray; P.A. Janaarthanan; U.K. Bhui; V. Bulusu; A. Smith; S. Misra; Sanjeev Kumar (Life Sciences in Space Research, 2026)

Correction: Statistical investigation of heatwave trends and change points in Telangana, India - Kona Naga Venkata Lakshmi Laasya; Supriya Kallakuri; Santosha Rathod; Lakshmi Neelima; Debasish Chakraborty; S. Vishnu Shankar; Mrinmoy Ray; Nobin Chandra Paul; Shahid Saleem; Ammaladinne Tharun Kumar; Nirmala Bandumula; Kirttiranjan Baral; et al. (Natural Hazards, 2026)

Recent hydroclimatic extremes in the Cypress Creek watershed, Texas, USA - N S Abeysingha; Ram L Ray (Journal of Earth System Science, 2026)

Divergence of Visual Morphology and Opsin Expression in an African Cichlid Linked With Turbidity - J. H. Tiarks; E. Ray; S. M. Gray (Molecular Ecology, 2026)
Turbidity is increasing in freshwaters globally due to human activities and is known to affect visually‐mediated behaviours in fish. As anthropogenic impacts continue to degrade aquatic environments, it is critical to determine how sensory systems are affected and what this might mean for population persistence. We investigated visual morphology and opsin gene expression in an African cichlid fish ( Pseudocrenilabrus multicolor ) that experiences environmental extremes across its East African range. We examined visual morphology (i.e., size of eyes and brain) and quantified retinal opsin gene expression of adult wild‐caught fish from two sites representing extremes of turbidity and oxygen (a high turbidity, high dissolved oxygen river and a low turbidity, low dissolved oxygen swamp). Further, we reared offspring of wild‐caught parents from each population in a full‐factorial high/low oxygen, high/low turbidity design to test for plasticity and tease apart the influence of each stressor individually and in combination. For wild‐caught fish, population drove variation in eye morphology and brain mass such that the river population had larger visual traits than the swamp population. Sex was an important driver for brain morphology with males having larger brains and optic tecta than females. All fish expressed the same cone opsin palette, comprised of sws2a , rh2a , and lws ; however, river fish expressed a higher proportion of lws opsin compared to swamp fish. Further, population significantly explained variation in lws opsin for males and trended toward significance in females. When major environmental stressors were examined in the rearing experiment, oxygen was a strong driver of eye and brain size. Cone opsin trends were less clear in the rearing experiment; the proportion of lws opsin in females significantly varied by the interactive effect of oxygen and turbidity, while sws2a opsin in males varied significantly by turbidity. This research improves our understanding of the effect of elevated turbidity on African cichlid vision and contributes to growing knowledge of how animals respond to human‐induced environmental change and multiple stressors.

Improved two stage triangular fuzzy STARMA model for drought forecasting in Southern Telangana - Ch. Preethi; A. Meena; Santosha Rathod; Balaji Naik B; S. Vishnu Shankar; Amit Saha; Mrinmoy Ray; Rahul Patil (Journal of Hydrology, 2026)

Statistical investigation of heatwave trends and change points in Telangana, India - Kona Naga Venkata Lakshmi Laasya; Supriya Kallakuri; Santosha Rathod; Lakshmi Neelima; Debasish Chakraborty; S. Vishnu Shankar; Mrinmoy Ray; Nobin Chandra Paul; Shahid Saleem; Ammaladinne Tharun Kumar; Nirmala Bandumula; Kirttiranjan Baral; et al. (Natural Hazards, 2026)

Age and geochemistry of carbonatites and associated silicate rocks in Sarnu-Dandali alkaline complex, Deccan Large Igneous Province: Evidence for melt immiscibility and plume-lithosphere interaction - Milan K. Mahala; Jyotiranjan S. Ray; Kanchan Pande (Contributions to Mineralogy and Petrology, 2026)

Effect of glass-fiber on mechanical performance and microstructure of bentonite-fly Ash and bentonite-sand mixes for landfill liner application - Chandra Bhanu Gupt; Ranita Ray; B. Giridhar Rajesh; S. Sreedeep (Bulletin of Engineering Geology and the Environment, 2026)

Letter to the Editor: Misclassification of fibres in Ramage et al. (2025) and implications for microplastics research - Kelly J. Sheridan; Richard S. Blackburn; Miranda T. Prendergast-Miller; Josephine Jones; Ray Palmer; Thomas Stanton (Chemosphere, 2025)

Systematic evaluation of Tox21 compounds that target β-adrenergic receptors and their role in cardiotoxicity - Xi Luo; Li Zhang; Srilatha Sakamuru; Precious A. Adesina; Jinghua Zhao; Menghang Xia; Tuan Xu; Deborah K. Ngan; Jameson Travers; Savannah Wood; Ray Sukhawanit; Anthony Garrison; et al. (Toxicology and Applied Pharmacology, 2025)

Coupling of metal fractionation with sediment quality in Mandovi and Zuari rivers, estuaries, and adjoining coastal area of Goa: Constrains on environmental risk - Krushna Vudamala; Sarang S. Deep; Durbar Ray; Karnan Chinnadurai; Kanakam Anil; Muralidhar Kocherla (Regional Studies in Marine Science, 2025)

Petrology and Geochemistry of Poikilitic Shergottite Northwest Africa 1950: bridging the gap between depleted and intermediate sources in Martian Mantle - Varsha M Nair; Amit Basu Sarbadhikari; G N S Sree Bhuvan; T. Vijaya Kumar; Nilanjana Sorcar; Sneha Mukherjee; E.V.S.S.K. Babu; Jyotiranjan S. Ray (Geochimica et Cosmochimica Acta, 2025)

Clinical Efficacy of Stem Cell Therapy in Neurotraumatic and Neurodegenerative Conditions: A Comparative Review - Jun Beom Ku; Ray J. Pak; Sarah S. Ku; Robert D. Holland; Han-Soo Kim (Tissue Engineering and Regenerative Medicine, 2025)

Manistee, a new Round-White Early to Mid-Season Maturing Potato Variety with Excellent Long-Term Storage Potential - David S. Douches; Joseph J. Coombs; William L. Behling; Ray Hammerschmidt; Greg E. Steere; Matthew L. Zuehlke; Christopher M. Long (American Journal of Potato Research, 2025)
Manistee is a round white chip-processing potato ( Solanum tuberosum ) variety developed for long-term storage. Evaluated as MSL292-A, Manistee is a selection from a cross between Snowden and the chip-processing breeding line MSH098-2. The tubers of Manistee are compressed, round with shallow eyes and early to mid-season maturity. Field testing and on-farm trials show that this variety has high yield potential with specific gravity comparable to Snowden and similar to better tolerance to blackspot bruise. Manistee was formally released in 2013 and has demonstrated reliable and excellent long-term storage chip-processing quality up to eight months post-harvest which extends the chip-processing storage season beyond Snowden. Furthermore, preliminary studies with Manistee, Snowden, Lamoka and Pike tuber disks demonstrated that Manistee started the wound healing process faster than Lamoka and Pike and slightly faster than Snowden which supports observations of stable and reliable commercial storage of the tubers for chip-processing.

Detection, isolation, and identification of Rhizoctonia theobromae associated with cassava witches’ broom disease in the Philippines - Darwin M. Landicho; Ray Jerome M. Montañez; Vicky S. Manayon; Ma Kristina Yzabelle C. Sendaydiego; Jestoni O. Gaylo; Amor C. Dimayacyac; Ikuo Sato; Daigo Takemoto; Marita S. Pinili; Sotaro Chiba (Physiological and Molecular Plant Pathology, 2025)

Effect of the garlic matrix and inclusion level on in vitro methane production and fermentation - N.F. Sari; S. Stergiadis; P.P. Ray; C. Rymer; L.A. Crompton; K.E. Kliem (Animal Feed Science and Technology, 2025)

Future hydro-climate extremes in the cypress creek watershed in Texas under different CMIP6 scenarios - N. S. Abeysingha; Ram L. Ray; Temesgen Gashaw Tarkegn (Sustainable Water Resources Management, 2025)

Complete mitochondrial DNA genome of the Indian Chhattisgarh duck and its phylogenetic analysis - Rajni Kumari; Ratna Prabha; Tirupati Rao Golla; P. K. Ray; Reena Kamal; Jaipal S. Choudhary; Abhay Kumar; Sanjay Kumar; Shanker Dayal; P. C. Chandran; Jyoti Kumar; M. K. Tripathi; et al. (Journal of Genetics, 2025)

Modelling Price Dynamics in Indian Potato Markets: A Comprehensive Econometric Approach - Rajeev Ranjan Kumar; S. Vishnu Shankar; Ronit Jaiswal; Jaiprakash Bisen; Kapil Choudhary; V. Lavanya; Mrinmoy Ray; K. N. Singh (Potato Research, 2025)

Retraction Note: Role of Polyamines in Molecular Regulation and Cross-Talks Against Drought Tolerance in Plants - Samapika Nandy; Saynati Mandal; Santosh Kumar Gupta; Uttpal Anand; Mimosa Ghorai; Avinash Mundhra; Md. Habibur Rahman; Puja Ray; Sicon Mitra; Durga Ray; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Journal of Plant Growth Regulation, 2025)

Optimal placement of wind turbines: a techno-economic analysis using real-time wind speed data and metaheuristic algorithms - M. M. Jaganath; S. Ray; N. B. D. Choudhury (International Journal of Energy and Water Resources, 2025)

Simultaneous Drought and Heatwave Events During Austral Summer in Northeast Brazil - Katyelle F. S. Bezerra; Helber B. Gomes; Hakki Baltaci; Pallav Ray; Janaíına P. Nascimento; Dirceu L. Herdies; Matheus J. A. Lyra; Maria Cristina L. Silva; Fabrício D. S. Silva; Cláudio M. Santos e Silva; Heliofábio B. Gomes (International Journal of Climatology, 2025)
The simultaneous occurrence of heatwaves and droughts is becoming more frequent and intense under climate change, particularly affecting vulnerable regions like Northeast Brazil (NEB). This study presents a comprehensive assessment of these compound extremes using long‐term in situ observations and ERA5 reanalysis. Heatwaves were defined by daily temperatures exceeding the 90th percentile, and droughts by the standardised precipitation index (SPI‐1). Results reveal substantial spatio‐temporal variability in these events, with sharp increases in frequency, duration, and intensity since the early 1990s–especially in 1998, 2006 and 2015, linked to La Niña and El Niño events. Atmospheric analyses showed positive temperature anomalies at 2 m, persistent negative specific humidity at multiple pressure levels, and contrasting circulation anomalies: positive flow at 850 hPa, negative at 500 hPa, and changes in divergence and vorticity. The semiarid region of the northeast was the most affected by drought, while the northeastern coast had higher frequencies of heatwaves, with longer durations. These findings highlight the complex interactions driving compound extremes in NEB and underscore the urgent need for regional adaptation and mitigation strategies.

Multiple anthelmintic drug resistance in the canine hookworm Ancylostoma caninum: AAVP position paper and research needs - Timothy G. Geary; Jason Drake; John S. Gilleard; Jeba R.J.Jesudoss Chelladurai; Pablo D. Jimenez Castro; Ray M. Kaplan; Antoinette E. Marsh; Craig R. Reinemeyer; Guilherme G. Verocai (Veterinary Parasitology, 2025)

Effects of climate and sea level change on sedimentation in the eastern Bengal Fan during the late Quaternary - A. Prajith; Jyotiranjan S. Ray; Bivin G. George; K.B. Joshi; R. Bhushan; R. Bhutani; Arvind Singh (Quaternary Science Reviews, 2025)

Performance of an oscillatory electrode reactor for electrochemical phosphate removal - Salil S. Mathew; Hassan G. Gomaa; Madhumita B. Ray (Journal of Environmental Chemical Engineering, 2025)

The role of TLRs (microbe recognition receptor) in gastric cancer: An update - Saade Abdalkareem Jasim; Sumaya Ayad Abdulrazzaq; H. Malathi; Suhaib Iqbal; Gaurav Sanghvi; E. Yulchiev; Subhashree Ray; S. Sunitha; Jawad Kadhim Ahmed; Ahmed Hussein Zwamel (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Enhancer zeste homolog 2 (EZH2) targeting by small interfering RNA (siRNA); recent advances and prospect - Chou-Yi Hsu; Abdulsalam Najm Mohammed; Ahmed Hjazi; Subasini Uthirapathy; Jyothi S. Renuka; Abhayveer Singh; Thyagarajan; Subhashree Ray; Hanen Mahmod Hulail (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Signal detection of ferric carboxymaltose-induced serious adverse events: disproportionality analysis of FAERS and VigiBase data and systematic review of case reports - Reddikumar Reddy Galigutta; Christy Thomas; Mahesh Rathod; P. N. Hasik; R. S. Ray; Jai Prakash; Krishna Undela (European Journal of Clinical Pharmacology, 2025)

A framework for sustainable urban settlement planning: Integrating geographic information system and multi-criteria decision analysis - S. K. Ray; A. Teja; S. Chaudhary; M. H. Kumar; R. Rahul; K. Rammohan; D. Himabindu (Environment, Development and Sustainability, 2025)

Geochronology of the Vindhyan Supergroup: Implications for the closure of the Proterozoic basins of India - Bivin G. George; Jyotiranjan S. Ray; Milan K. Mahala; J. Amal Dev; J.K. Tomson; J. Haripriya; Alok Kumar (Precambrian Research, 2025)

Terrebonne Basin, Gulf of Mexico gas hydrate resource evaluation and 3-D modeling of basin-scale sedimentation, salt tectonics, and hydrate system evolution since the early Miocene - Laura N. Dafov; Zachary F.M. Burton; Seth S. Haines; Allegra Hosford Scheirer; Nicole Masurek; Ray Boswell; Matthew Frye; Yongkoo Seol; Stephan A. Graham (Marine and Petroleum Geology, 2025)

Socio-economic impacts and responses of the fishing industry and fishery managers to changes in small pelagic fish distribution and abundance - Felipe J. Quezada-Escalona; Desiree Tommasi; Isaac C. Kaplan; Pierre-Yves Hernvann; Timothy H. Frawley; Dorleta Garcia; Leire Ibaibarriaga; Sonia Sánchez-Maroño; Carryn de Moor; Jennifer Beckensteiner; Amy M. Schueller; Diana Feijó; et al. (Reviews in Fish Biology and Fisheries, 2025)
Small Pelagic Fish (SPF) exhibit large fluctuations in abundance and distribution in response to environmental variability. To maintain the resilience of fishing communities and develop effective and equitable climate adaptation strategies, improved understanding of how the fishing industry responds to spatio-temporal shifts within and across SPF populations is of critical importance. In this paper, we examine the responses of the fishing industry and resource managers to shifts in SPF availability worldwide and identify the resulting socioeconomic impacts. Leveraging SPF case studies from around the globe, we synthesize and compare the social-ecological linkages and feedbacks mediating how SPF fisheries respond to changes in marine ecosystem structure and function associated with (1) spatial shifts in species distribution and habitat availability, (2) ‘boom and bust’ population dynamics, or (3) changes in fish size and quality. Our case studies illustrate multiple paths towards the resilience of small pelagic fisheries and the fishing industry dependent upon them while emphasizing the need for increased coordination and cooperation across sectors and scales as climate change progresses. Drawing from the lessons offered by historical responses, as environmental variability increases, efforts to increase the flexibility and dynamism of SPF harvest portfolios and management strategies, licensing regimes, and international catch and allocation agreements may be required to ensure resource sustainability and human well-being.

Retraction Note: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2025)

Tracing the Footprint of Microplastics: Transport Mechanism, Degradation, and Remediation in Marine Environment - Arkadeep Mukherjee; Shivani Kumar S; Randeep Singh; Sangeetha D; Young-Ho Ahn; Saikat Sinha Ray (Water, Air, & Soil Pollution, 2025)

The Kopargaon LL5 chondrite: A new fall of monomict breccia from India - D Ray; S Sarkar; A Das; G Arora; A D Shukla; Anil Bhardwaj (Journal of Earth System Science, 2025)

Prospective ecological contributions of potential marine OECMs and MPAs to enhance marine conservation in Indonesia - Estradivari; Indah Kartika; Dedi S. Adhuri; Luky Adrianto; Firdaus Agung; Gabby N. Ahmadia; Sonia Bejarano; Stuart J. Campbell; Faridz Rizal Fachri; Hari Kushardanto; Cliff Marlessy; Beby Pane; et al. (Ocean & Coastal Management, 2024)

Electrocatalytic synergies of melt-quenched Ni-Sn-Se-Te nanoalloy for direct seawater electrolysis - John D. Rodney; Sindhur Joshi; Subhasmita Ray; Lavanya Rao; S. Deepapriya; Karel Carva; Badekai Ramachandra Bhat; N.K. Udayashankar; Suresh Perumal; Sadhana Katlakunta; C. Justin Raj; Byung Chul Kim (Chemical Engineering Journal, 2024)

Sedimentary ancient DNA sequences reveal marine ecosystem shifts and indicator taxa for glacial-interglacial sea ice conditions - Danielle Magann Grant; Kristine Steinsland; Tristan Cordier; Ulysses S. Ninnemann; Umer Zeeshan Ijaz; Håkon Dahle; Stijn De Schepper; Jessica Louise Ray (Quaternary Science Reviews, 2024)

Geochemical and Isotopic evidence for volcanism on the Alleppey Terrace, southwest Indian continental margin - Reji Srinivas; M.K. Sreeraj; A. Prajith; Bivin G. George; Jyotiranjan S. Ray (Continental Shelf Research, 2024)

Effects of increasing soil moisture on Antarctic desert microbial ecosystems - Eden Zhang; Sin Yin Wong; Paul Czechowski; Aleks Terauds; Angelique E. Ray; Nicole Benaud; Devan S. Chelliah; Daniel Wilkins; Kate Montgomery; Belinda C. Ferrari (Conservation Biology, 2024)
Overgeneralization and a lack of baseline data for microorganisms in high‐latitude environments have restricted the understanding of the microbial response to climate change, which is needed to establish Antarctic conservation frameworks. To bridge this gap, we examined over 17,000 sequence variants of bacteria and microeukarya across the hyperarid Vestfold Hills and Windmill Islands regions of eastern Antarctica. Using an extended gradient forest model, we quantified multispecies response to variations along 79 edaphic gradients to explore the effects of change and wind‐driven dispersal on community dynamics under projected warming trends. We also analyzed a second set of soil community data from the Windmill Islands to test our predictions of major environmental tipping points. Soil moisture was the most robust predictor for shaping the regional soil microbiome; the highest rates of compositional turnover occurred at 10–12% soil moisture threshold for photoautotrophs, such as Cyanobacteria , Chlorophyta , and Ochrophyta . Dust profiles revealed a high dispersal propensity for Chlamydomonas , a microalga, and higher biomass was detected at trafficked research stations. This could signal the potential for algal blooms and increased nonendemic species dispersal as human activities increase in the region. Predicted increases in moisture availability on the Windmill Islands were accompanied by high photoautotroph abundances. Abundances of rare oligotrophic taxa, such as Eremiobacterota and Candidatus Dormibacterota, which play a crucial role in atmospheric chemosynthesis, declined over time. That photosynthetic taxa increased as soil moisture increased under a warming scenario suggests the potential for competition between primary production strategies and thus a more biotically driven ecosystem should the climate become milder. Better understanding of environmental triggers will aid conservation efforts, and it is crucial that long‐term monitoring of our study sites be established for the protection of Antarctic desert ecosystems. Furthermore, the successful implementation of an improved gradient forest model presents an exciting opportunity to broaden its use on microbial systems globally.

Editorial Expression of Concern: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

The development of early farming diets and population change in the Maya region and their climate context - Erin E. Ray; Nadia C. Neff; Paige Lynch; Jose Mes; Matthew S. Lachniet; Douglas J. Kennett; Keith M. Prufer (Quaternary International, 2024)

Does urbanisation lead to parallel demographic shifts across the world in a cosmopolitan plant? - Aude E. Caizergues; James S. Santangelo; Rob W. Ness; Fabio Angeoletto; Daniel N. Anstett; Julia Anstett; Fernanda Baena‐Diaz; Elizabeth J. Carlen; Jaime A. Chaves; Mattheau S. Comerford; Karen Dyson; Mohsen Falahati‐Anbaran; et al. (Molecular Ecology, 2024)
Urbanisation is occurring globally, leading to dramatic environmental changes that are altering the ecology and evolution of species. In particular, the expansion of human infrastructure and the loss and fragmentation of natural habitats in cities is predicted to increase genetic drift and reduce gene flow by reducing the size and connectivity of populations. Alternatively, the ‘urban facilitation model’ suggests that some species will have greater gene flow into and within cities leading to higher diversity and lower differentiation in urban populations. These alternative hypotheses have not been contrasted across multiple cities. Here, we used the genomic data from the GLobal Urban Evolution project (GLUE), to study the effects of urbanisation on non‐adaptive evolutionary processes of white clover ( Trifolium repens ) at a global scale. We found that white clover populations presented high genetic diversity and no evidence of reduced N e linked to urbanisation. On the contrary, we found that urban populations were less likely to experience a recent decrease in effective population size than rural ones. In addition, we found little genetic structure among populations both globally and between urban and rural populations, which showed extensive gene flow between habitats. Interestingly, white clover displayed overall higher gene flow within urban areas than within rural habitats. Our study provides the largest comprehensive test of the demographic effects of urbanisation. Our results contrast with the common perception that heavily altered and fragmented urban environments will reduce the effective population size and genetic diversity of populations and contribute to their isolation.

Flood risk index mapping in data scarce region by considering GIS and MCDA (FRI mapping in data scarce region by considering GIS and MCDA) - S. K. Ray (Environment, Development and Sustainability, 2024)

Bacterial multi-enzyme signature assessment for wastewater reclamation and ecological resilience in tropical waste stabilization pond - S. Khan; A. Ray; J. N. Bhakta; S. Lahiri Ganguly (International Journal of Environmental Science and Technology, 2024)

Helicobacter pylori and Epstein-Barr virus infection in cell polarity alterations - Budhadev Baral; Meenakshi Kandpal; Anushka Ray; Ankit Jana; Dhirendra Singh Yadav; Kumar Sachin; Amit Mishra; Mirza S. Baig; Hem Chandra Jha (Folia Microbiologica, 2024)

HydroShare retrospective: Science and technology advances of a comprehensive data and model publication environment for the water science domain - David G. Tarboton; Daniel P. Ames; Jeffery S. Horsburgh; Jonathan L. Goodall; Alva Couch; Richard Hooper; Jerad Bales; Shaowen Wang; Anthony Castronova; Martin Seul; Ray Idaszak; Zhiyu Li; et al. (Environmental Modelling & Software, 2024)

Identification of Suitable Sites for Water Harvesting Structures in Jamsholaghat Sub-basin Using GIS and Multi-Criteria Decision Analysis - S. K. Ray; V. R. Desai (Journal of the Indian Society of Remote Sensing, 2024)

Identifying the groundwater potential zones in Jamsholaghat sub-basin by considering GIS and multi-criteria decision analysis - S. K. Ray (International Journal of Environmental Science and Technology, 2024)

Analysis of localized features during wet and dry rainfall episodes over southern tip of India - E. A. Resmi; B. Preethi; R. S. Ajayamohan; Pallav Ray; C. K. Unnikrishnan; S. Nita; R. K. Sumesh; J. Dharmadas (International Journal of Climatology, 2023)
The large spatial and temporal variability of wet and dry spells of the Indian Summer Monsoon (ISM) poses the great challenge in understanding and predicting monsoonal rainfall. This challenge is further exacerbated over smaller regions, such as the southern tip of India, which receives the first spell of ISM rainfall. In this study, the characteristic features and possible precursors for wet and dry spells of rainfall over the southern tip of India are investigated. We also explore the variability in monsoon low‐level jet (LLJ) in relation to wet and dry spells over a coastal station Thiruvananthapuram (8.48°N, 76.95°E) in southwest India using in situ observations and other ancillary datasets. The results show that a wet spell spanning 3–4 days contributes about 30% of seasonal rainfall. Wet spells are characterized by westerly wind anomaly in the southern tip of India and easterly wind anomaly in northern India, leading to anomalous cyclonic vorticity over the Indian subcontinent. The opposite happens during dry spells. These characteristics are prominent from 2 days prior to the initiation of the spells, suggesting they may be used as precursors for forecasting wet and dry spells over Thiruvananthapuram. Analysis of low‐ to mid‐tropospheric (2 and 4 km) humidity reveals significant moistening (drying) during wet (dry) spells. Yet, both wet and dry spells experience humid (>80%) boundary layer. The differences in mid‐level humidity and thermodynamical structures between wet and dry spells seem to contribute to distinct rainfall characteristics over the southern tip of India. These results indicate that the use of in situ observations along with large‐scale reanalysis datasets may provide valuable information on the precursors for wet and dry spells over the southern tip of India, which can help both in regional‐ and city‐level planning and management of water resources.

Negative δ13Ccarb excursions within early part of the Lomagundi event recorded in the Paleoproterozoic sedimentary carbonates, Aravalli Supergroup, Rajasthan India: Chemostratigraphy and basin evolution - Abhisikta Goswami; Shushanta Sarangi; Sarada P. Mohanty; Dattatray J. Patil; Anindya Sarkar; Jyoti S. Ray; Satyabrata Das; Debadutta Mohanty; S. Masood Ahmad; Rudra M. Pradhan; Arijit Barik (Precambrian Research, 2023)

A water-absorbent hydrogel prepared with arabinoxylans from flaxseed (Linum usitatissimum) and galactomannans from subabul (Leucaena leucocephala) impacts the growth and composition of cherry tomatoes in potted experiments - Aratrika Ray; Abhinav Sharma; Rekha S. Singhal (Journal of Cleaner Production, 2023)

Offsets in tide-gauge reference levels detected by satellite altimetry: ten case studies - R. D. Ray; M. J. Widlansky; A. S. Genz; P. R. Thompson (Journal of Geodesy, 2023)
Comparing measurements of absolute sea level by satellite altimetry and relative sea level by a tide gauge can reveal errors in either measurement system. Combining the measurements can determine vertical land motion (VLM) at the tide gauge. We here discuss ten case studies in which a tide gauge has likely experienced a small ( $$\le 10$$ ≤ 10 cm), discontinuous offset in the vertical, suggesting inadvertent loss of reference-level stability. Proper interpretation of offsets is helped if independent VLM measurements from nearby geodetic stations are available. In two cases, earthquake-induced VLM cannot be ruled out, although it appears unlikely. Offsets as small as 1–2 cm can be detected when both altimeter and tide gauge successfully observe the same ocean signal. This is most likely to occur for tide gauges located on small, open-ocean islands. Tide gauges near large land masses are typically more challenging owing to inadequacies of satellite altimetry near land and to differences between coastal and open-ocean sea levels. The case studies highlight the utility of satellite altimetry for tide-gauge quality control.

Hydrogel formulation based on galactomannan from residual spent coffee ground confers bioactivities and viscosifying properties in milkshake - Aratrika Ray; Rekha S. Singhal (Food Bioscience, 2023)

Atmospheric dynamics impact on urban-ozone variability over the Indo-Gangetic Plain under very low anthropogenic emission - D. Ray; S. Raha (International Journal of Environmental Science and Technology, 2023)

Pb-Pb age of the Gotan Limestone, Marwar Supergroup: Implications for Ediacaran-Cambrian transition events in the peninsular India - Bivin G. George; Milan K. Mahala; Jyotiranjan S. Ray (Precambrian Research, 2023)

RETRACTED ARTICLE: Role of Polyamines in Molecular Regulation and Cross-Talks Against Drought Tolerance in Plants - Samapika Nandy; Saynati Mandal; Santosh Kumar Gupta; Uttpal Anand; Mimosa Ghorai; Avinash Mundhra; Md. Habibur Rahman; Puja Ray; Sicon Mitra; Durga Ray; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Journal of Plant Growth Regulation, 2023)

Dynamics of physico-chemical properties towards understanding the optimum ageing of basmati and non-basmati rice (Oryza sativa L.) for consumer preferences - Swapnil S. Thakare; Monika Awana; Sunil I. Warwate; Shreya Mandal; Shalini Gaur Rudra; Haritha Bollinedi; Mrinmoy Ray; Amolkumar U. Solanke; Lekshmy Sathy Nair; Suresh Kumar; Veda Krishnan; Archana Singh (Journal of Cereal Science, 2023)

Impact of relative humidity and temperature oscillations mimicking authentic storage during shipping on whey proteins powders properties - J. Burgain; G. Francius; L. Cvetkovska; C. Paris; M. Alexander; C. Ray; S. El-Kirat-Chatel; C. Gaiani (Food Structure, 2023)

Structure and composition of natural ferrihydrite nano-colloids in anoxic groundwater - Maya Engel; Vincent Noël; Samuel Pierce; Libor Kovarik; Ravi K. Kukkadapu; Juan S. Lezama Pacheco; Odeta Qafoku; J. Ray Runyon; Jon Chorover; Weijiang Zhou; John Cliff; Kristin Boye; et al. (Water Research, 2023)

World Association for the Advancement of Veterinary Parasitology (W.A.A.V.P.) guideline for diagnosing anthelmintic resistance using the faecal egg count reduction test in ruminants, horses and swine - Ray M. Kaplan; Matthew J. Denwood; Martin K. Nielsen; Stig M. Thamsborg; Paul R. Torgerson; John S. Gilleard; Robert J. Dobson; Jozef Vercruysse; Bruno Levecke (Veterinary Parasitology, 2023)

Cytogenetic Diversity in Scilloideae (Asparagaceae): a Comprehensive Recollection and Exploration of Karyo-Evolutionary Trends - Sayantani Nath; Sayantika Sarkar; Sayali D. Patil; Partha Sarathi Saha; Manoj M. Lekhak; Sudipta Ray; Satyawada Rama Rao; S. R. Yadav; R. C. Verma; Manoj K. Dhar; S. N. Raina; Sumita Jha (The Botanical Review, 2023)

Morphological and molecular clue resolves confusion in Pisodonophis boro complex with re-description of Pisodonophis boro (Hamilton 1822) from type locality and description of a new species from India - Swarup Ranjan Mohanty; Rajesh Kumar Behera; Smrutirekha Acharya; Lipika Patnaik; Dipanjan Ray; Jaya Kishor Seth; Shesdev Patro; Subhrendu S. Mishra; Anil Mohapatra (Marine Biodiversity, 2023)

Rise and fall of SARS-CoV-2 variants in Rotterdam: Comparison of wastewater and clinical surveillance - Ray W. Izquierdo-Lara; Leo Heijnen; Bas B. Oude Munnink; Claudia M.E. Schapendonk; Goffe Elsinga; Jeroen Langeveld; Johan Post; Divyae K. Prasad; Christian Carrizosa; Frederic Been; Janko van Beek; Remy Schilperoort; et al. (Science of The Total Environment, 2023)

C-Sr-Pb isotope systematics of the carbonate sequences of Kaladgi Supergroup, India: Implications for basin evolution and correlation with Proterozoic global events - Bivin G. George; Jyotiranjan S. Ray; Shilpa Patil Pillai; Milan K. Mahala; Sanjeev Kumar; Vivek S. Kale (Precambrian Research, 2023)

Seasonal variability in size-resolved hygroscopicity of sub-micron aerosols over the Western Ghats, India: Closure and parameterization - Avishek Ray; G. Pandithurai; S. Mukherjee; V. Anil Kumar; A. Hazra; Rohit D. Patil; V. Waghmare (Science of The Total Environment, 2023)

The Miller 03356 IVA iron: Insights into the formation mechanism of microplessite - D. Ray; S. Ghosh; M. Paliwal; S. Mishra; J. Jha (Planetary and Space Science, 2023)

A Meta-Analysis of the Genome-Wide Association Studies on Two Genetically Correlated Phenotypes Suggests Four New Risk Loci for Headaches - Weihua Meng; Parminder S. Reel; Charvi Nangia; Aravind Lathika Rajendrakumar; Harry L. Hebert; Qian Guo; Mark J. Adams; Hua Zheng; Zen Haut Lu; Debashree Ray; Lesley A. Colvin; Colin N. A. Palmer; et al. (Phenomics, 2023)
Headache is one of the commonest complaints that doctors need to address in clinical settings. The genetic mechanisms of different types of headache are not well understood while it has been suggested that self-reported headache and self-reported migraine were genetically correlated. In this study, we performed a meta-analysis of genome-wide association studies (GWAS) on the self-reported headache phenotype from the UK Biobank and the self-reported migraine phenotype from the 23andMe using the Unified Score-based Association Test (metaUSAT) software for genetically correlated phenotypes ( N = 397,385). We identified 38 loci for headaches, of which 34 loci have been reported before and four loci were newly suggested. The LDL receptor related protein 1 ( LRP1 )— Signal Transducer and Activator of Transcription 6 ( STAT6 )— S hort chain D ehydrogenase / R eductase family 9C member 7 ( SDR9C7 ) region in chromosome 12 was the most significantly associated locus with a leading p value of 1.24 × 10 –62 of rs11172113. The One Cut homeobox 2 ( ONECUT2 ) gene locus in chromosome 18 was the strongest signal among the four new loci with a p value of 1.29 × 10 –9 of rs673939. Our study demonstrated that the genetically correlated phenotypes of self-reported headache and self-reported migraine can be meta-analysed together in theory and in practice to boost study power to identify more variants for headaches. This study has paved way for a large GWAS meta-analysis involving cohorts of different while genetically correlated headache phenotypes.

Assessment of extreme rainfall through statistical process control-I chart - N S Abeysingha; K M Kularathna; A M K R Bandara; Ram L Ray (Journal of Earth System Science, 2023)

Co-extraction of turmeric (Curcuma longa L.) and dried coconut shreds by supercritical fluid extraction (SFE): Chemical and bioactivity profile - Abhinav Sharma; Aratrika Ray; Rekha S. Singhal (Journal of Cleaner Production, 2023)

State-of-the-art review of fluidized bed stripper internals - Allan S. Issangya; Ray Cocco; Jia Wei Chew (Chemical Engineering Journal, 2023)

Sustainable Growing Areas for Sugarcane in Sri Lanka Under a Changing Climate - D. M. B. M. Deegala; N. S. Abeysingha; L. P. Muthuwatta; Ram L. Ray (Sugar Tech, 2022)

A GIS-based Spatial Prediction of Landslide Hazard Zones and Mapping in an Eastern Himalayan Hilly Region Using Large Scale Soil Mapping and Analytical Hierarchy Process - R. Srinivasan; D. Vasu; S. Amar Suputhra; Rajendra Hegde; S. K. Ray; S. K. Singh (Journal of the Indian Society of Remote Sensing, 2022)

Affecting behavioural change through empowerment: conceptual insights from theory and agricultural case studies in South Asia - Serena H. Hamilton; Wendy S. Merritt; Lucy Carter; Arnab Chakraborty; Michaela Cosijn; Lilly Lim-Camacho; Rajeshwar Mishra; Geoff Syme; Mahanambrota Das; Dhananjay Ray (Regional Environmental Change, 2022)
Affecting behavioural change is a common underlying goal across environmental and agricultural sciences, from climate change mitigation and adaptation, biodiversity conservation, water management, to crop diversification. However, many projects fail to drive or sustain change despite sound science and good intentions. This paper draws on existing theories of behavioural change to construct a conceptual framework that explores pathways to initiate and sustain change through the lens of empowerment, self-efficacy and agency. The framework is demonstrated with case studies from a project in India and Bangladesh that examined social inclusion of marginalised and poor farmers in the context of intensifying agriculture. The framework and case studies highlight that a number of conditions are needed to affect meaningful change including that target beneficiaries are suitably motivated, believe in their own capability and power to enact change and have access to the necessary resources. We propose the framework as a tool to help project teams explore the underlying elements of the process of change when designing, implementing and assessing agricultural or environmental projects and interventions. We contend that behavioural and social change needs to be explicitly fostered in such endeavours to achieve better and longer-term outcomes for the people and environment.

HPV Vaccine Intent among Adult Women Receiving Care at Community Health Centers - M. L. Hecht; R. BeLue; A. Ray; S. Hopfer; M. Miller-Day; F. Mckee (Journal of Cancer Education, 2022)

Anti-parasitic activity of the Olea europaea and Ficus carica on Leishmania major: new insight into the anti-leishmanial agents - Abolghasem Siyadatpanah; Farzaneh Mirzaei; Rajib Hossain; Mohammad Torequl Islam; Marziye Fatemi; Roghayeh Norouzi; Masoumeh Gholami Koohestan; Fatemeh Namdar; Ray S. Almeida; Mohammad S. Mubarak; Reza Saberi; Henrique Douglas Melo Coutinho (Biologia, 2022)

Bridge to the future: Important lessons from 20 years of ecosystem observations made by the OzFlux network - Jason Beringer; Caitlin E. Moore; Jamie Cleverly; David I. Campbell; Helen Cleugh; Martin G. De Kauwe; Miko U. F. Kirschbaum; Anne Griebel; Sam Grover; Alfredo Huete; Lindsay B. Hutley; Johannes Laubach; et al. (Global Change Biology, 2022)
In 2020, the Australian and New Zealand flux research and monitoring network, OzFlux, celebrated its 20 th anniversary by reflecting on the lessons learned through two decades of ecosystem studies on global change biology. OzFlux is a network not only for ecosystem researchers, but also for those ‘next users’ of the knowledge, information and data that such networks provide. Here, we focus on eight lessons across topics of climate change and variability, disturbance and resilience, drought and heat stress and synergies with remote sensing and modelling. In distilling the key lessons learned, we also identify where further research is needed to fill knowledge gaps and improve the utility and relevance of the outputs from OzFlux. Extreme climate variability across Australia and New Zealand (droughts and flooding rains) provides a natural laboratory for a global understanding of ecosystems in this time of accelerating climate change. As evidence of worsening global fire risk emerges, the natural ability of these ecosystems to recover from disturbances, such as fire and cyclones, provides lessons on adaptation and resilience to disturbance. Drought and heatwaves are common occurrences across large parts of the region and can tip an ecosystem's carbon budget from a net CO 2 sink to a net CO 2 source. Despite such responses to stress, ecosystems at OzFlux sites show their resilience to climate variability by rapidly pivoting back to a strong carbon sink upon the return of favourable conditions. Located in under‐represented areas, OzFlux data have the potential for reducing uncertainties in global remote sensing products, and these data provide several opportunities to develop new theories and improve our ecosystem models. The accumulated impacts of these lessons over the last 20 years highlights the value of long‐term flux observations for natural and managed systems. A future vision for OzFlux includes ongoing and newly developed synergies with ecophysiologists, ecologists, geologists, remote sensors and modellers.

Equilibrium, kinetic and hydraulic study of different Indian bentonites in presence of lead - Saswati Ray; Anil Kumar Mishra; Ajay S. Kalamdhad (European Journal of Environmental and Civil Engineering, 2022)

Biochemical profile of resurrection fern allies: Selaginella wightii Hieron and Selaginella involvens (S.W.) Spring - V. Kalaiarasi; Ray S. Almeida; Henrique D. M. Coutinho; M. Johnson (Vegetos, 2022)

Disorders of Tetrahydrobiopterin Metabolism: Experience from South India - Somdattaa Ray; Hansashree Padmanabha; Vykuntaraju K. Gowda; Rohan Mahale; Rita Christopher; Shruthy Sreedharan; Debjyoti Dhar; Mahesh Kamate; Madhu Nagappa; Maya Bhat; Rammurthy Anjanappa; Gautham Arunachal; et al. (Metabolic Brain Disease, 2022)

Valorization of waste potato peel as iron adsorbent and catalyst in photo-oxidation: a sustainable waste management strategy - P. Dey; R. Koijam; S. Ray (International Journal of Environmental Science and Technology, 2022)

Challenges of forecasting rainfall associated with tropical cyclones in India - Kamaljit Ray; S. Balachandran; Sushil K. Dash (Meteorology and Atmospheric Physics, 2022)

Applications of Advanced Geospatial Technology for Expansion of Area under Horticultural Crops in North Eastern Region of India - B. K. Handique; C. Goswami; P. Jena; F. Dutta; R. Samiam; I. Nongrum; D. Jha; P. L. N. Raju; C. R. Deka; R. Sarma; K. Sarmah; H. K. Dutta; et al. (Journal of the Indian Society of Remote Sensing, 2022)

Assimilation of Remote Sensing Data into Crop Growth Model for Yield Estimation: A Case Study from India - Murali Krishna Gumma; M. D. M. Kadiyala; Pranay Panjala; Shibendu S. Ray; Venkata Radha Akuraju; Sunil Dubey; Andrew P. Smith; Rajesh Das; Anthony M. Whitbread (Journal of the Indian Society of Remote Sensing, 2022)

Seasonal variations in the water quality and antibiotic resistance of microbial pollution indicators in the Mandovi and Zuari estuaries, Goa, India - Ashwini D. Toraskar; Cathrine S. Manohar; Charmaine L. Fernandes; Durbar Ray; Abigayle D. Gomes; Ajit Antony (Environmental Monitoring and Assessment, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Evaluating Connections Between Nitrogen Cycling and the Macrofauna in Native Oyster Beds in a New England Estuary - S. G. Ayvazian; Nicholas E. Ray; Anna Gerber-Williams; Sinead Grabbert; Adam Pimenta; Boze Hancock; Donald Cobb; Charles Strobel; R. W. Fulweiler (Estuaries and Coasts, 2022)

Field-Level Crop Classification Using an Optimal Dataset of Multi-temporal Sentinel-1 and Polarimetric RADARSAT-2 SAR Data with Machine Learning Algorithms - Neetu; Pritam Meshram; S. S. Ray (Journal of the Indian Society of Remote Sensing, 2021)

Geo-spatial analysis for horizontal and vertical variability of bulk density, particle-size distribution and soil moisture content in Tripura, Northeastern India - Sah Kausar Reza; Nirmal Kumar; Sundaram Ramachandran; Subrata Mukhopadhyay; Surendra Kumar Singh; Brahma S. Dwivedi; Sanjay Kumar Ray (Arabian Journal of Geosciences, 2021)

Impact of real and simulated municipal solid waste leachates on the hydraulic and swelling behaviour of bentonites for landfill application - Saswati Ray; Anil Kumar Mishra; Ajay S. Kalamdhad; Chejarla Venkatesh Reddy (Environmental Monitoring and Assessment, 2021)

Breeding latitude is associated with the timing of nesting and migration around the annual calendar among Purple Martin (Progne subis) populations - L. R. Neufeld; S. Muthukumarana; J. D. Fischer; J. D. Ray; J. Siegrist; K. C. Fraser (Journal of Ornithology, 2021)

Barren Island volcanism and seismicity: An intriguing finding - Goutham Krishna Teja Gunda; Prashant Kumar Champati Ray; Mamta Chauhan; Prakash Chauhan; S Balaji (Journal of Earth System Science, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Active and weakening MJO events in the Maritime Continent - Bradford S. Barrett; Casey R. Densmore; Pallav Ray; Elizabeth R. Sanabia (Climate Dynamics, 2021)
To better understand the Madden–Julian Oscillation (MJO) in the Maritime Continent (MC), events from 1980 to 2019 were classified as active or weakening according to propagation characteristics and amplitude changes in two leading indices, the Real-time Multivariate MJO (RMM) index and Outgoing Longwave Radiation (OLR) MJO Index (OMI). Active MJO events had larger index amplitudes than weakening events, and those amplitude differences appeared at day − 3 in the RMM and day − 8 in the OMI and remained through day + 15 in both indices (day 0 marked the day an event entered the MC). Thus, active events were stronger than weakening events as they approached and crossed the MC. To understand differences in environments between these events, composites of OLR and specific humidity were compared for each. Active MJO events had consistently more negative OLR anomalies and greater specific humidity in both the boundary layer and free troposphere than weakening MJO events. Those differences persisted during both easterly and westerly phases of the Quasi-biennial Oscillation (QBO) and during La Niña and El Niño. Active MJO events during QBO westerly winds had more specific humidity than active events did during QBO easterly winds. Finally, both active and weakening MJO events featured a diurnal cycle of lower-tropospheric specific humidity over land areas of the MC, and the amount of atmospheric moisture available to active events was consistently greater than weakening ones. These results indicate that index amplitude, OLR, and tropospheric specific humidity can all be important tools in identifying active and weakening MJO events in the MC, including for different phases of the QBO and the El Niño-Southern Oscillation (ENSO).

Influence of real and synthetic municipal solid waste leachates on consolidation and shear strength behaviour of bentonites - Saswati Ray; Anil Kumar Mishra; Ajay S. Kalamdhad (Environmental Science and Pollution Research, 2021)

Assessment of groundwater depletion–induced land subsidence and characterisation of damaging cracks on houses: a case study in Mohali-Chandigarh area, India - Neha Kadiyan; R. S. Chatterjee; Pranshu Pranjal; Pankaj Agrawal; S. K. Jain; M. L. Angurala; A. K. Biyani; M. S. Sati; Dheeraj Kumar; Ashutosh Bhardwaj; P. K. Champati Ray (Bulletin of Engineering Geology and the Environment, 2021)

Depositional history of the Mesoproterozoic Chhattisgarh Basin, central India: insights from geochemical provenance of siliciclastic sediments - Bivin G. George; Jyotiranjan S. Ray (International Geology Review, 2021)

Crop Situation in India, Before, During and After COVID-19 Lockdown, as Seen from the Satellite Data of Resourcesat-2 AWiFS - Shalini Saxena; Amit Rabha; Preeti Tahlani; Shibendu S. Ray (Journal of the Indian Society of Remote Sensing, 2021)

β-Adrenoceptor blockade prevents carotid body hyperactivity and elevated vascular sympathetic nerve density induced by chronic intermittent hypoxia - Abdulaziz A. Alzahrani; Lily L. Cao; Hayyaf S. Aldossary; Demitris Nathanael; Jiarong Fu; Clare J. Ray; Keith L. Brain; Prem Kumar; Andrew M. Coney; Andrew P. Holmes (Pflügers Archiv - European Journal of Physiology, 2021)
Carotid body (CB) hyperactivity promotes hypertension in response to chronic intermittent hypoxia (CIH). The plasma concentration of adrenaline is reported to be elevated in CIH and our previous work suggests that adrenaline directly activates the CB. However, a role for chronic adrenergic stimulation in mediating CB hyperactivity is currently unknown. This study evaluated whether beta-blocker treatment with propranolol (Prop) prevented the development of CB hyperactivity, vascular sympathetic nerve growth and hypertension caused by CIH. Adult male Wistar rats were assigned into 1 of 4 groups: Control (N), N + Prop, CIH and CIH + Prop. The CIH paradigm consisted of 8 cycles h −1 , 8 h day −1 , for 3 weeks. Propranolol was administered via drinking water to achieve a dose of 40 mg kg −1 day −1 . Immunohistochemistry revealed the presence of both β 1 and β 2 -adrenoceptor subtypes on the CB type I cell. CIH caused a 2–3-fold elevation in basal CB single-fibre chemoafferent activity and this was prevented by chronic propranolol treatment. Chemoafferent responses to hypoxia and mitochondrial inhibitors were attenuated by propranolol, an effect that was greater in CIH animals. Propranolol decreased respiratory frequency in normoxia and hypoxia in N and CIH. Propranolol also abolished the CIH mediated increase in vascular sympathetic nerve density. Arterial blood pressure was reduced in propranolol groups during hypoxia. Propranolol exaggerated the fall in blood pressure in most (6/7) CIH animals during hypoxia, suggestive of reduced sympathetic tone. These findings therefore identify new roles for β-adrenergic stimulation in evoking CB hyperactivity, sympathetic vascular hyperinnervation and altered blood pressure control in response to CIH.

Contribution of IRS-1C Data to Agricultural Monitoring: A Review - Shibendu S. Ray; Raghavendra P. Singh; Karan Choudhary (Journal of the Indian Society of Remote Sensing, 2021)

Monitoring agricultural drought using combined drought index in India - N Chattopadhyay; K Malathi; Nivedita Tidke; S D Attri; Kamaljit Ray (Journal of Earth System Science, 2020)

The Palaeogene record of Himalayan erosion in the Andaman Basin - Neeraj Awasthi; Jyotiranjan S Ray (Journal of Earth System Science, 2020)

Understanding the bias in surface latent and sensible heat fluxes in contemporary AGCMs over tropical oceans - Xin Zhou; Pallav Ray; Bradford S. Barrett; Pang-Chi Hsu (Climate Dynamics, 2020)

Genetic analysis of downy mildew resistance and identification of molecular markers linked to resistance gene Ppa207 on chromosome 2 in cauliflower - Partha Saha; Chandrika Ghoshal; Soham Ray; Namita Das Saha; Mohita Srivastava; Pritam Kalia; B. S. Tomar (Euphytica, 2020)

Risk chart for identification of potential landslide due to the presence of residual soil - Arunava Ray; R. E. S. Chaitanya Kumar; Rajesh Rai; Suprakash Gupta (Natural Hazards, 2020)

A rapid and sensitive method to detect SARS-CoV-2 virus using targeted-mass spectrometry - Praveen Singh; Rahul Chakraborty; Robin Marwal; V. S. Radhakrishan; Akash Kumar Bhaskar; Himanshu Vashisht; Mahesh S. Dhar; Shalini Pradhan; Gyan Ranjan; Mohamed Imran; Anurag Raj; Uma Sharma; et al. (Journal of Proteins and Proteomics, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Cancer mortality risk, fine particulate air pollution, and smoking in a large, representative cohort of US adults - Nathan C. Coleman; Richard T. Burnett; Joshua D. Higbee; Jacob S. Lefler; Ray M. Merrill; Majid Ezzati; Julian D. Marshall; Sun-Young Kim; Matthew Bechle; Allen L. Robinson; C. Arden Pope (Cancer Causes & Control, 2020)

Identification of quantitative trait loci for carbon isotope ratio (δ13C) in a recombinant inbred population of soybean - Sumandeep K. Bazzer; Avjinder S. Kaler; Jeffery D. Ray; James R. Smith; Felix B. Fritschi; Larry C. Purcell (Theoretical and Applied Genetics, 2020)

Role of topography on the MJO in the maritime continent: a numerical case study - Haochen Tan; Pallav Ray; Bradford S. Barrett; Mukul Tewari; Mitchell W. Moncrieff (Climate Dynamics, 2020)

John Leonard Bannister 1937–2018 - Robert L. Brownell; Doug S. Butterworth; Catherine M. Kemper; Martin Cawthorn; Michael Double; Greg P. Donovan; Ray Gambell; Hidehiro Kato (Marine Mammal Science, 2020)

Plastics in municipal drinking water and wastewater treatment plant effluents: challenges and opportunities for South Africa—a review - Austine O.C. Iroegbu; Rotimi E. Sadiku; Suprakas S. Ray; Yskandar Hamam (Environmental Science and Pollution Research, 2020)

Effects of integrated farming system and rainwater harvesting on livelihood improvement in North-Eastern region of India compared to traditional shifting cultivation: evidence from an action research - Sanjay Kumar Ray; Dibyendu Chatterjee; D. J. Rajkhowa; S. K. Baishya; S. Hazarika; S. Paul (Agroforestry Systems, 2020)

Cellular and molecular mechanisms of curcumin in prevention and treatment of disease - Sita Sharan Patel; Ashish Acharya; R. S. Ray; Ritesh Agrawal; Ramsaneh Raghuwanshi; Priyal Jain (Critical Reviews in Food Science and Nutrition, 2020)

Bioaccumulation of vanadium (V), niobium (Nb) and tantalum (Ta) in diverse mangroves of the Indian Sundarbans - R. Ray; B. Dutta; S. K. Mandal; A. G. González; O. S. Pokrovsky; T. K. Jana (Plant and Soil, 2020)

Thunderstorm dynamics through wind profiling features: the first observation by stratospheric-tropospheric radar of GU - M. Devi; S. Patgiri; A. Medhi; S. Das; M. Saikia; A. K. Barbara; S. S. Kakatkar; K. P. Ray (Natural Hazards, 2020)

Choosing best practices for managing impacts of trawl fishing on seabed habitats and biota - Robert A. McConnaughey; Jan G. Hiddink; Simon Jennings; C. Roland Pitcher; Michel J. Kaiser; Petri Suuronen; Marija Sciberras; Adriaan D. Rijnsdorp; Jeremy S. Collie; Tessa Mazor; Ricardo O Amoroso; Ana M. Parma; et al. (Fish and Fisheries, 2020)
Bottom trawling accounts for almost one quarter of global fish landings but may also have significant and unwanted impacts on seabed habitats and biota. Management measures and voluntary industry actions can reduce these impacts, helping to meet sustainability objectives for fisheries, conservation and environmental management. These include changes in gear design and operation of trawls, spatial controls, impact quotas and effort controls. We review nine different measures and actions and use published studies and a simple conceptual model to evaluate and compare their performance. The risks and benefits of these management measures depend on the extent to which the fishery is already achieving management objectives for target stocks and the characteristics of the management system that is already in place. We offer guidance on identifying best practices for trawl‐fisheries management and show that best practices and their likelihood of reducing trawling impacts depend on local, national and regional management objectives and priorities, societal values and resources for implementation. There is no universal best practice, and multiple management measures and industry actions are required to meet sustainability objectives and improve trade‐offs between food production and environmental protection.

The pharmacokinetics of 3-fluoroamphetamine following delivery using clinically relevant routes of administration - Ying Jiang; Azizi Ray; Mohammad Shajid Ashraf Junaid; Sonalika Arup Bhattaccharjee; Kayla Kelley; Ajay K. Banga; Bruce E. Blough; Kevin S. Murnane (Drug Delivery and Translational Research, 2020)

Evolution of the Proterozoic Vindhyan Basin, Rajasthan, India: insights from geochemical provenance of siliciclastic sediments - Anil D. Shukla; Bivin G. George; Jyotiranjan S. Ray (International Geology Review, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Diversity of hepatitis C virus infection among HIV-infected people who inject drugs in India - S. S. Solomon; D. Boon; S. Saravanan; A. K. Srikrishnan; C. K. Vasudevan; P. Balakrishnan; D. Persaud; S. C. Ray; S. Mehta; S. H. Mehta (VirusDisease, 2019)

Enhanced Production of Shigella flexneri Polysaccharide from a Newly Devised Silicate Method as a Potential Vaccine Conjugate - P. V. S. L. S. S. Narayana; Jayati Ray Dutta (Current Microbiology, 2019)

Prolonged exposure to manure from livestock‐administered antibiotics decreases ecosystem carbon‐use efficiency and alters nitrogen cycling - Carl Wepking; Brian Badgley; John E. Barrett; Katharine F. Knowlton; Jane M. Lucas; Kevan J. Minick; Partha P. Ray; Sarah E. Shawver; Michael S. Strickland (Ecology Letters, 2019)
Microbial communities drive soil ecosystem function but are also susceptible to environmental disturbances. We investigated whether exposure to manure sourced from cattle either administered or not administered antibiotics affected microbially mediated terrestrial ecosystem function. We quantified changes in microbial community composition via amplicon sequencing, and terrestrial elemental cycling via a stable isotope pulse‐chase. Exposure to manure from antibiotic‐treated cattle caused: (i) changes in microbial community structure; and (ii) alterations in elemental cycling throughout the terrestrial system. This exposure caused changes in fungal : bacterial ratios, as well as changes in bacterial community structure. Additionally, exposure to manure from cattle treated with pirlimycin resulted in an approximate two‐fold increase in ecosystem respiration of recently fixed‐carbon, and a greater proportion of recently added nitrogen in plant and soil pools compared to the control manure. Manure from antibiotic‐treated cattle therefore affects terrestrial ecosystem function via the soil microbiome, causing decreased ecosystem carbon use efficiency, and altered nitrogen cycling.

CO2 uptake and chlorophyll a fluorescence of Suaeda fruticosa grown under diurnal rhythm and after transfer to continuous dark - Silas Wungrampha; Rohit Joshi; Ray S. Rathore; Sneh L. Singla-Pareek; Govindjee; Ashwani Pareek (Photosynthesis Research, 2019)

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Integration of satellite remote sensing and geophysical techniques (electrical resistivity tomography and ground penetrating radar) for landslide characterization at Kunjethi (Kalimath), Garhwal Himalaya, India - Suresh Kannaujiya; Shovan Lal Chattoraj; Dilhani Jayalath; Prashant Kumar Champati ray; Kushank Bajaj; Shilpika Podali; M. P. S. Bisht (Natural Hazards, 2019)

Beneficial Changes in Capsicum frutescens Due to Priming by Plant Probiotic Burkholderia spp. - Rohini Sabu; R. Aswani; K. S. Nidheesh; J.G. Ray; A. Remakanthan; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Co-digestion of Biowastes to Enhance Biological Hydrogen Process by Defined Mixed Bacterial Cultures - Sanjay K. S. Patel; Subhasree Ray; Jyotsana Prakash; Ji Hyang Wee; Sang-Yong Kim; Jung-Kul Lee; Vipin Chandra Kalia (Indian Journal of Microbiology, 2019)

Probing the effect of a room temperature ionic liquid on phospholipid membranes in multilamellar vesicles - S. Mitra; D. Ray; G. Bhattacharya; R. Gupta; D. Sen; V. K. Aswal; S. K. Ghosh (European Biophysics Journal, 2019)

State of rare earth elements in the sediment and their bioaccumulation by mangroves: a case study in pristine islands of Indian Sundarban - Sanjay K. Mandal; Raghab Ray; Aridane G. González; Vasileios Mavromatis; Oleg S. Pokrovsky; Tapan K. Jana (Environmental Science and Pollution Research, 2019)

Stability of expression of Cry1Ac and Cry2Ab2 proteins in Bollgard-II hybrids at different stages of crop growth in different genotypes across cropping seasons and multiple geographies - Anik Luke Dhanaraj; Alan Ray Willse; S. P. Kamath (Transgenic Research, 2019)

Comprehensive review on treatment of high-strength distillery wastewater in advanced physico-chemical and biological degradation pathways - S. Ghosh Ray; M. M. Ghangrekar (International Journal of Environmental Science and Technology, 2019)

Remote Sensing-Based Yield Forecasting for Sugarcane (Saccharum officinarum L.) Crop in India - S. K. Dubey; A. S. Gavli; S. K. Yadav; Seema Sehgal; S. S. Ray (Journal of the Indian Society of Remote Sensing, 2018)

Utilization of low-grade banded hematite jasper ores: recovery of iron values and production of ferrosilicon - Nigamananda Ray; Deepak Nayak; Nilima Dash; Swagat S. Rath (Clean Technologies and Environmental Policy, 2018)

Correction to: High CO2 absorption of O-carboxymethylchitosan synthesised from chitosan - Pradeep Kumar; Ekta Faujdar; Raj K. Singh; Subham Paul; Aruna Kukrety; Vijay K. Chhibber; Siddharth S. Ray (Environmental Chemistry Letters, 2018)

High CO2 absorption of O-carboxymethylchitosan synthesised from chitosan - Pradeep Kumar; Ekta Faujdar; Raj K. Singh; Subham Paul; Aruna Kukrety; Vijay K. Chhibber; Siddharth S. Ray (Environmental Chemistry Letters, 2018)

Antidepressant and anxiolytic like effects of Urtica dioica leaves in streptozotocin induced diabetic mice - Sita Sharan Patel; R. S. Ray; Arun Sharma; Vineet Mehta; Anju Katyal; Malairaman Udayabanu (Metabolic Brain Disease, 2018)

Association mapping identifies loci for canopy temperature under drought in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; Antonio R. Asebedo; C. Andy King; E. E. Gbur; Larry C. Purcell (Euphytica, 2018)

Response of benthic fauna to experimental bottom fishing: A global meta‐analysis - Marija Sciberras; Jan Geert Hiddink; Simon Jennings; Claire L Szostek; Kathryn M Hughes; Brian Kneafsey; Leo J Clarke; Nick Ellis; Adriaan D Rijnsdorp; Robert A McConnaughey; Ray Hilborn; Jeremy S Collie; et al. (Fish and Fisheries, 2018)
Bottom‐contact fishing gears are globally the most widespread anthropogenic sources of direct disturbance to the seabed and associated biota. Managing these fishing disturbances requires quantification of gear impacts on biota and the rate of recovery following disturbance. We undertook a systematic review and meta‐analysis of 122 experiments on the effects‐of‐bottom fishing to quantify the removal of benthos in the path of the fishing gear and to estimate rates of recovery following disturbance. A gear pass reduced benthic invertebrate abundance by 26% and species richness by 19%. The effect was strongly gear‐specific, with gears that penetrate deeper into the sediment having a significantly larger impact than those that penetrate less. Sediment composition (% mud and presence of biogenic habitat) and the history of fishing disturbance prior to an experimental fishing event were also important predictors of depletion, with communities in areas that were not previously fished, predominantly muddy or biogenic habitats being more strongly affected by fishing. Sessile and low mobility biota with longer life‐spans such as sponges, soft corals and bivalves took much longer to recover after fishing (>3 year) than mobile biota with shorter life‐spans such as polychaetes and malacostracans (

Phosphorus Budget of the Sundarban Mangrove Ecosystem: Box Model Approach - R. Ray; N. Majumder; C. Chowdhury; S. Das; T. K. Jana (Estuaries and Coasts, 2018)

Priority Zoning of Available Micronutrients in the Soils of Agro-ecological Sub-regions of North-East India Using Geo-spatial Techniques - Siladitya Bandyopadhyay; Prasenjit Ray; Shelton Padua; S. Ramachandran; Roomesh Kumar Jena; Partha Deb Roy; D. P. Dutta; Surendra Kumar Singh; Sanjay Kumar Ray (Agricultural Research, 2018)

Semi-empirical model for retrieval of soil moisture using RISAT-1 C-Band SAR data over a sub-tropical semi-arid area of Rewari district, Haryana (India) - Kishan Singh Rawat; Vinay Kumar Sehgal; Sanatan Pradhan; Shibendu S Ray (Journal of Earth System Science, 2018)

Ecology of Endomycorrhizal Association in Musa spp. of South India - K. S. Nidheesh; N. Valsalakumar; V. P. Potty; J. G. Ray (Symbiosis, 2018)

Vitamin D3 attenuates cognitive deficits and neuroinflammatory responses in ICV-STZ induced sporadic Alzheimer’s disease - P. Yamini; R. S. Ray; Kanwaljit Chopra (Inflammopharmacology, 2018)

Protective effects of the resveratrol analog piceid in dopaminergic SH-SY5Y cells - Sneha Potdar; Mayur S. Parmar; Sidhartha D. Ray; Jane E. Cavanaugh (Archives of Toxicology, 2018)

Earthquake induced liquefaction hazard, probability and risk assessment in the city of Kolkata, India: its historical perspective and deterministic scenario - Sankar Kumar Nath; Nishtha Srivastava; Chitralekha Ghatak; Manik Das Adhikari; Ambarish Ghosh; S. P. Sinha Ray (Journal of Seismology, 2018)

Effect of Rainfall Variability on Rice Yield in North Eastern Hills of India: A Case Study - Deotrephy K. Dkhar; S. M. Feroze; Ram Singh; Lala I. P. Ray (Agricultural Research, 2017)

Proton Induced Modulation of ICT and PET Processes in an Imidazo-phenanthroline Based BODIPY Fluorophores - Shrikant S. Thakare; Goutam Chakraborty; Shantaram Kothavale; Soumyaditya Mula; Alok K. Ray; Nagaiyan Sekar (Journal of Fluorescence, 2017)

Incorporating field wind data to improve crop evapotranspiration parameterization in heterogeneous regions - Ray G. Anderson; Jorge F. S. Ferreira; Dennise L. Jenkins; Nildo da Silva Dias; Donald L. Suarez (Irrigation Science, 2017)

Genome-wide association mapping of canopy wilting in diverse soybean genotypes - Avjinder S. Kaler; Jeffery D. Ray; William T. Schapaugh; C. Andy King; Larry C. Purcell (Theoretical and Applied Genetics, 2017)

Retrieval and validation of soil moisture from FRS-1 data set of radar imaging satellite (RISAT-1) - Kishan Singh Rawat; Vinay Kumar Sehgal; Sanatan Pradhan; Shibendu S. Ray (Arabian Journal of Geosciences, 2017)

Human activity was a major driver of the mid‐Holocene vegetation change in southern Cumbria: implications for the elm decline in the British Isles - Mark J. Grosvenor; Richard T. Jones; Chris S. M. Turney; Dan J. Charman; Alan Hogg; Dave Coward; Ray Wilson (Journal of Quaternary Science, 2017)
The dramatic decline in elm ( Ulmus ) across a large swathe of north‐west Europe in the mid‐Holocene has been ascribed to a number of possible factors, including climate change, human activity and/or pathogens. A major limitation for identifying the underlying cause(s) has been the limited number of high‐resolution records with robust geochronological frameworks. Here, we report a multiproxy study of an upland (Blea Tarn) and lowland (Urswick Tarn) landscape in southern Cumbria (British Isles) to reconstruct vegetation change across the elm decline in an area with a rich and well‐dated archaeological record to disentangle different possible controls. Here we find a two‐stage decline in Ulmus taking place between 6350–6150 and 6050–5850 cal a BP, with the second phase coinciding with an intensification of human activity. The scale of the decline and associated human impact is more abrupt in the upland landscape. We consider it likely that a combination of human impact and disease drove the Ulmus decline within southern Cumbria.

Crustal deformation rates in Assam Valley, Shillong Plateau, Eastern Himalaya, and Indo-Burmese region from 11 years (2002–2013) of GPS measurements - Prakash Barman; Sridevi Jade; T. S. Shrungeshwara; Ashok Kumar; Sanjeev Bhattacharyya; Jagat Dwipendra Ray; Saigeetha Jagannathan; Wangshi Menla Jamir (International Journal of Earth Sciences, 2017)

RNA processing body (P-body) dynamics in mesophyll protoplasts re-initiating cell division - Dilbag S. Bhullar; Michael B. Sheahan; Ray J Rose (Protoplasma, 2017)

S- and Sr-isotopic compositions in barite–silica chimney from the Franklin Seamount, Woodlark Basin, Papua New Guinea: constraints on genesis and temporal variability of hydrothermal fluid - Durbar Ray; Ranadip Banerjee; S. Balakrishnan; Anil L. Paropkari; Subir Mukhopadhyay (International Journal of Earth Sciences, 2017)

Transcriptomic effects of adenosine 2A receptor deletion in healthy and endotoxemic murine myocardium - Kevin J. Ashton; Melissa E. Reichelt; S. Jamal Mustafa; Bunyen Teng; Catherine Ledent; Lea M. D. Delbridge; Polly A. Hofmann; R. Ray Morrison; John P. Headrick (Purinergic Signalling, 2017)

Lessons from the Far End: Caterpillar FRASS-Induced Defenses in Maize, Rice, Cabbage, and Tomato - Swayamjit Ray; Saumik Basu; Loren J. Rivera-Vega; Flor E. Acevedo; Joe Louis; Gary W. Felton; Dawn S. Luthe (Journal of Chemical Ecology, 2016)

Betrayal: radio-tagged Burmese pythons reveal locations of conspecifics in Everglades National Park - Brian J. Smith; Michael S. Cherkiss; Kristen M. Hart; Michael R. Rochford; Thomas H. Selby; Ray W. Snow; Frank J. Mazzotti (Biological Invasions, 2016)

Expression of a rice GLP in Medicago truncatula exerting pleiotropic effects on resistance against Fusarium oxysporum through enhancing FeSOD-like activity - Tasawar Sultana; Farah Deeba; Farah Naz; Ray J. Rose; S. M. Saqlan Naqvi (Acta Physiologiae Plantarum, 2016)

The future of nemertean taxonomy (phylum Nemertea) — a proposal - Per Sundberg; Sónia C. S. Andrade; Thomas Bartolomaeus; Patrick Beckers; Jörn von Döhren; Daria Krämer; Ray Gibson; Gonzalo Giribet; Alfonso Herrera‐Bachiller; Juan Junoy; Hiroshi Kajihara; Sebastian Kvist; et al. (Zoologica Scripta, 2016)

Metabarcoding and metabolome analyses of copepod grazing reveal feeding preference and linkage to metabolite classes in dynamic microbial plankton communities - Jessica L. Ray; Julia Althammer; Katrine S. Skaar; Paolo Simonelli; Aud Larsen; Diane Stoecker; Andrey Sazhin; Umer Z. Ijaz; Christopher Quince; Jens C. Nejstgaard; Marc Frischer; Georg Pohnert; et al. (Molecular Ecology, 2016)
In order to characterize copepod feeding in relation to microbial plankton community dynamics, we combined metabarcoding and metabolome analyses during a 22‐day seawater mesocosm experiment. Nutrient amendment of mesocosms promoted the development of haptophyte ( Phaeocystis pouchetii )‐ and diatom ( Skeletonema marinoi )‐dominated plankton communities in mesocosms, in which Calanus sp. copepods were incubated for 24 h in flow‐through chambers to allow access to prey particles ( P. pouchetii , were passively consumed or even negatively selected according to our indicator. Our analysis of the relationship between Calanus grazing ratios and intracellular metabolite profiles indicates the importance of carbohydrates and lipids in plankton succession and copepod–prey interactions. This molecular characterization of Calanus sp. grazing therefore provides new evidence for selective feeding in mixed plankton assemblages and corroborates previous findings that copepod grazing may be coupled to the developmental and metabolic stage of the entire prey community rather than to individual prey abundances.

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Increased risk of cardiovascular disease in premenopausal female ragpickers of Eastern India: involvement of inflammation, oxidative stress, and platelet hyperactivity - Nandan Kumar Mondal; Sanghita Roychoudhury; Sayali Mukherjee; Shabana Siddique; Madhuchanda Banerjee; Mark S. Slaughter; Twisha Lahiri; Manas Ranjan Ray (Molecular and Cellular Biochemistry, 2016)

Genome-wide association of familial prostate cancer cases identifies evidence for a rare segregating haplotype at 8q24.21 - Craig C. Teerlink; Daniel Leongamornlert; Tokhir Dadaev; Alun Thomas; James Farnham; Robert A. Stephenson; Shaun Riska; Shannon K. McDonnell; Daniel J. Schaid; William J. Catalona; S. Lilly Zheng; Kathleen A. Cooney; et al. (Human Genetics, 2016)

Radioelemental, petrological and geochemical characterization of the Bundelkhand craton, central India: implication in the Archaean geodynamic evolution - Labani Ray; P. Nagaraju; S. P. Singh; G. Ravi; Sukanta Roy (International Journal of Earth Sciences, 2016)

Impact of WWII dumpsites on Saipan (CNMI): heavy metal status of soils and sediments - Gary R. W. Denton; Carmen A. Emborski; April A. B. Hachero; Ray S. Masga; John A. Starmer (Environmental Science and Pollution Research, 2016)

NSDF: Neuroscience Simulation Data Format - Subhasis Ray; Chaitanya Chintaluri; Upinder S. Bhalla; Daniel K. Wójcik (Neuroinformatics, 2016)

Morphotectonic and petrological variations along the southern Central Indian Ridge - Ranadhir Mukhopadhyay; Sridhar D. Iyer; Dwijesh Ray; S. M. Karisiddaiah; Rajendra K. Drolia (International Journal of Earth Sciences, 2016)

Kedarnath disaster 2013: causes and consequences using remote sensing inputs - P. K. Champati Ray; Shovan Lal Chattoraj; M. P. S. Bisht; Suresh Kannaujiya; Kamal Pandey; Ajanta Goswami (Natural Hazards, 2016)

Multi-view stereophotogrammetry for post-mastectomy breast reconstruction - Xiangyang Ju; Helga Henseler; Matthew Jian-qiao Peng; Balvinder S. Khambay; Arup K. Ray; Ashraf F. Ayoub (Medical & Biological Engineering & Computing, 2016)

Preparation and characterization of gum karaya hydrogel nanocomposite flocculant for metal ions removal from mine effluents - E. Fosso-Kankeu; H. Mittal; F. Waanders; I. O. Ntwampe; S. S. Ray (International Journal of Environmental Science and Technology, 2016)

First Record of Rama Rao’s Scorpionfish, Scorpaenopsis ramaraoi Randall and Eschmeyer, 2001 (Family: Scorpaenidae) from Indian Waters - Dipanjan Ray; Subhrendu S. Mishra; Anil Mohapatra (Proceedings of the Zoological Society, 2015)

Real‐time spatial management approaches to reduce bycatch and discards: experiences from Europe and the United States - Alyson S Little; Coby L Needle; Ray Hilborn; Daniel S Holland; C Tara Marshall (Fish and Fisheries, 2015)
Spatial management measures are currently being used to manage bycatch and discards, given the spatial heterogeneity of fish distributions. However, permanent fishing closures are often poorly implemented, unresponsive to stock dynamics and do not achieve their management objectives. Recently, real‐time spatial management tools for managing bycatch and discards implemented under either a comanagement or self‐governance approach have been introduced in Europe and the US . Real‐time catch and discard information is shared among fishers to incentivise and encourage vessels to leave areas of high bycatch. Here, the similarities and differences, in governance, implementation and management of ten real‐time spatial management systems from across Europe and the US are reviewed. A framework is developed to characterize the attributes associated with voluntary, private and regulatory real‐time spatial management tools. Challenges and management practices in the different case studies are reviewed providing insights for designing these spatial management tools. The results illustrate that real‐time spatial management approaches can create incentives for fishers to develop, use and share information and technology to avoid undesired catch. Compared with Europe, the US has developed spatial management tools with more truly real‐time mechanisms and with greater involvement of the fishing industry in designing and operating the tools.

Examining common assumptions about recruitment: a meta‐analysis of recruitment dynamics for worldwide marine fisheries - Cody S Szuwalski; Katyana A Vert‐Pre; André E Punt; Trevor A Branch; Ray Hilborn (Fish and Fisheries, 2015)
Assumptions about the future productivity of a stock are necessary to calculate sustainable catches in fisheries management. Fisheries scientists often assume the number of young fish entering a population (recruitment) is related to the biomass of spawning adults and that recruitment dynamics do not change over time. Thus, managers often use a target biomass based on spawning biomass as the basis for calculating sustainable catches. However, we show recruitment and spawning biomass are not positively related over the observed range of stock sizes for 61% of 224 stocks in the RAM Legacy Stock Assessment Database. Furthermore, 85% of stocks for which spawning biomass may not drive recruitment dynamics over the observed ranges exhibit shifts in average recruitment, which is often used in proxies for target biomasses. Our results suggest that the environment more strongly influences recruitment than spawning biomass over the observed stock sizes for many stocks. Management often endeavours to maintain stock sizes within the observed ranges, so methods for setting management targets that include changes within an ecosystem may better define the status of some stocks, particularly as climate changes.

Analysis and Potential Alternatives for the Disputed South China Sea from Ocean Governance in the Polar Regions - Ray Tsung-Han Tai; Nathaniel S. Pearre; Shih-Ming Kao (Coastal Management, 2015)

Maize Plants Recognize Herbivore-Associated Cues from Caterpillar Frass - Swayamjit Ray; Iffa Gaffor; Flor E. Acevedo; Anjel Helms; Wen-Po Chuang; John Tooker; Gary W. Felton; Dawn S. Luthe (Journal of Chemical Ecology, 2015)

Life at the leading edge: genetic impoverishment of the spotted bass, Micropterus punctulatus, at its Western edge - J. W. Ray; M. Husemann; D. J. Lutz-Carrillo; R. S. King; P. D. Danley (Environmental Biology of Fishes, 2015)

40Ar/39Ar geochronology of subaerial lava flows of Barren Island volcano and the deep crust beneath the Andaman Island Arc, Burma Microplate - Jyotiranjan S. Ray; Kanchan Pande; Rajneesh Bhutani (Bulletin of Volcanology, 2015)

A review of iron species for visible-light photocatalytic water purification - Russell S. Jack; Godwin A. Ayoko; Moses O. Adebajo; Ray L. Frost (Environmental Science and Pollution Research, 2015)

Peralkaline felsic magmatism at the Nemrut volcano, Turkey: impact of volcanism on the evolution of Lake Van (Anatolia) IV - Ray Macdonald; Mari Sumita; Hans-Ulrich Schmincke; Bogusław Bagiński; John C. White; Sławomir S. Ilnicki (Contributions to Mineralogy and Petrology, 2015)

Development and Characterization of Sorbitan Monostearate and Sesame Oil-Based Organogels for Topical Delivery of Antimicrobials - Vinay K. Singh; Krishna Pramanik; Sirsendu S. Ray; Kunal Pal (AAPS PharmSciTech, 2015)

Geochemistry of PGE in mafic rocks of east Khasi Hills, Shillong Plateau, NE India - Sampa Hazra; Jyotisankar Ray; C Manikyamba; Abhishek Saha; S S Sawant (Journal of Earth System Science, 2015)

Colonization of Solidago altissima by the Specialist Aphid Uroleucon nigrotuberculatum: Effects of Genetic Identity and Leaf Chemistry - Ray S. Williams; Megan A. Avakian (Journal of Chemical Ecology, 2015)

Small-scale variability in water storage and plant available water in shallow, rocky soils - Ieyasu Tokumoto; James L. Heilman; Susanne Schwinning; Kevin J. McInnes; Marcy E. Litvak; Cristine L. S. Morgan; Ray H. Kamps (Plant and Soil, 2014)

Microbial Biomass Carbon Status in Agro-Ecological Sub Regions of Black Soils in India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Assessment of organochlorine pesticide residues in Indian flue-cured tobacco with gas chromatography-single quadrupole mass spectrometer - Rakesh Kumar Ghosh; Zareen S. Khan; C. V. N. Rao; Kaushik Banerjee; D. Damodar Reddy; T. G. K. Murthy; Nalli Johnson; Deb Prasad Ray (Environmental Monitoring and Assessment, 2014)

Engineered chromosome-based genetic mapping establishes a 3.7 Mb critical genomic region for Down syndrome-associated heart defects in mice - Chunhong Liu; Masae Morishima; Xiaoling Jiang; Tao Yu; Kai Meng; Debjit Ray; Annie Pao; Ping Ye; Michael S. Parmacek; Y. Eugene Yu (Human Genetics, 2014)

Developing Spectral Library of Major Plant Species of Western Himalayas Using Ground Observations - K. R. Manjunath; Amit Kumar; Mehra Meenakshi; R. Renu; S. K. Uniyal; R. D. Singh; P. S. Ahuja; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

Removal of nitrate and COD from wastewater using denitrification process: kinetic, optimization, and statistical studies - Sanak Ray; Ayusman Mohanty; S. S. Mohanty; Snehasish Mishra; G. Roy Chaudhury (Clean Technologies and Environmental Policy, 2014)

A Study to Evaluate Lipid Profile in Treatment Naïve HIV Positive Patients - Anitha Devanath; Somdattaa Ray; Ravi Kumar; B. S. Prarthana (Indian Journal of Clinical Biochemistry, 2014)

Occupancy patterns of large mammals in the Far North of Ontario under imperfect detection and spatial autocorrelation - Lucy G. Poley; Bruce A. Pond; James A. Schaefer; Glen S. Brown; Justina C. Ray; Devin S. Johnson (Journal of Biogeography, 2014)
Aim An understanding of the factors that influence species distributions in heterogeneous landscapes is important when making decisions regarding conservation. Moreover, occupancy probabilities based on detection data can reveal important species–habitat relationships. Accounting for the spatial autocorrelation of detection data increases the statistical validity of occupancy models, but is not often considered. Using novel occupancy modelling that explicitly incorporates detectability and spatial autocorrelation, we assessed the influence of habitat on occupancy patterns of woodland caribou ( Rangifer tarandus caribou ), moose ( Alces alces ) and wolves ( Canis lupus ) across a broad biogeographical extent where fire is the dominant agent of disturbance. Location Northern Ontario, Canada. Methods We aerially surveyed 3851 sampling units, each covering 100 km 2 , for woodland caribou, moose and wolves in February–March in 2009, 2010 and 2011, and visited 1663 units more than once to estimate detectability. We used restricted spatial regression to model occupancy probabilities of each species with respect to habitat factors in two ecozones, accounting for both imperfect detection and lack of independence of sampling units. Results Covariates influencing species detection varied among ecozones and species. Caribou occupancy was positively related to bogs and negatively related to disturbed areas, while moose occupancy showed opposite responses to these covariates. Wolf occupancy was related to high prey occupancy. Explicitly accounting for spatial autocorrelation in detection data reduced the chance of type I error in occupancy estimates compared with non‐spatial models. Main conclusions Habitat relationships and occupancy patterns support the hypothesis that caribou remain spatially segregated from moose to reduce predation risk. The broad scale of analysis indicated changes in species–habitat relationships, suggesting that limiting factors vary across biogeographical gradients. The spatial pattern in caribou occupancy allowed us to identify important areas used by caribou across the region, including the ecotone between fire‐driven boreal forests and peatland complexes. The evidence for significant relationships between caribou and land cover, predators and alternate prey underscores the need for careful planning of development and infrastructure in the area.

Urease Activity in Various Agro-ecological Sub-regions of Black Soil Regions of India - Kulandaivelu Velmourougane; M. V. Venugopalan; T. Bhattacharyya; Dipak Sarkar; D. K. Pal; Apeksha Sahu; P. Chandran; S. K. Ray; Champa Mandal; K. M. Nair; Jagdish Prasad; R. S. Singh; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2013)

Age and geochemistry of the Newania dolomite carbonatites, India: implications for the source of primary carbonatite magma - Jyotiranjan S. Ray; Kanchan Pande; Rajneesh Bhutani; Anil D. Shukla; Vinai K. Rai; Alok Kumar; Neeraj Awasthi; R. S. Smitha; Dipak K. Panda (Contributions to Mineralogy and Petrology, 2013)

Iron cycling at corroding carbon steel surfaces - Jason S. Lee; Joyce M. McBeth; Richard I. Ray; Brenda J. Little; David Emerson (Biofouling, 2013)

Isolation and characterization of potent bioactive fraction with antioxidant and UV absorbing activity from Aloe barbadensis Miller gel - Anirban Ray; S. Dutta Gupta; Sampad Ghosh (Journal of Plant Biochemistry and Biotechnology, 2013)

Comparative pharmacokinetics of PAMAM-OH dendrimers and HPMA copolymers in ovarian tumor-bearing mice - S. Sadekar; O. Linares; G. J. Noh; D. Hubbard; A. Ray; M. Janát-Amsbury; C. M. Peterson; J. Facelli; H. Ghandehari (Drug Delivery and Translational Research, 2013)

Effect of Age and Exercise on the Viscoelastic Properties of Rat Tail Tendon - Andrew S. LaCroix; Sarah E. Duenwald-Kuehl; Stacey Brickson; Tiffany L. Akins; Gary Diffee; Judd Aiken; Ray Vanderby; Roderic S. Lakes (Annals of Biomedical Engineering, 2013)

Urban air-quality assessment and source apportionment studies for Bhubaneshwar, Odisha - Parth Sarathi Mahapatra; Sanak Ray; Namrata Das; Ayusman Mohanty; T. S. Ramulu; Trupti Das; G. Roy Chaudhury; S. N. Das (Theoretical and Applied Climatology, 2013)

Implication of Organic Matter on Arsenic and Antimony Sequestration in Sediment: Evidence from Sundarban Mangrove Forest, India - S. K. Mandal; R. Ray; C. Chowdhury; N. Majumder; T. K. Jana (Bulletin of Environmental Contamination and Toxicology, 2013)

Directional genomic hybridization for chromosomal inversion discovery and detection - F. Andrew Ray; Erin Zimmerman; Bruce Robinson; Michael N. Cornforth; Joel S. Bedford; Edwin H. Goodwin; Susan M. Bailey (Chromosome Research, 2013)

Spatial occupancy models for large data sets - Devin S. Johnson; Paul B. Conn; Mevin B. Hooten; Justina C. Ray; Bruce A. Pond (Ecology, 2013)
Since its development, occupancy modeling has become a popular and useful tool for ecologists wishing to learn about the dynamics of species occurrence over time and space. Such models require presence–absence data to be collected at spatially indexed survey units. However, only recently have researchers recognized the need to correct for spatially induced overdisperison by explicitly accounting for spatial autocorrelation in occupancy probability. Previous efforts to incorporate such autocorrelation have largely focused on logit‐normal formulations for occupancy, with spatial autocorrelation induced by a random effect within a hierarchical modeling framework. Although useful, computational time generally limits such an approach to relatively small data sets, and there are often problems with algorithm instability, yielding unsatisfactory results. Further, recent research has revealed a hidden form of multicollinearity in such applications, which may lead to parameter bias if not explicitly addressed. Combining several techniques, we present a unifying hierarchical spatial occupancy model specification that is particularly effective over large spatial extents. This approach employs a probit mixture framework for occupancy and can easily accommodate a reduced‐dimensional spatial process to resolve issues with multicollinearity and spatial confounding while improving algorithm convergence. Using open‐source software, we demonstrate this new model specification using a case study involving occupancy of caribou ( Rangifer tarandus ) over a set of 1080 survey units spanning a large contiguous region (108 000 km 2 ) in northern Ontario, Canada. Overall, the combination of a more efficient specification and open‐source software allows for a facile and stable implementation of spatial occupancy models for large data sets.

Agricultural Area Diversification and Crop Water Demand Analysis: A Remote Sensing and GIS Approach - B. U. Choudhury; Anil Sood; S. S. Ray; P. K. Sharma; S. Panigrahy (Journal of the Indian Society of Remote Sensing, 2013)

Temporal Healing in Rat Achilles Tendon: Ultrasound Correlations - Connie S. Chamberlain; Sarah E. Duenwald-Kuehl; Gregory Okotie; Sabrina H. Brounts; Geoffrey S. Baer; Ray Vanderby (Annals of Biomedical Engineering, 2013)

Mitigating future climate change effects by shifting planting dates of crops in rice–wheat cropping system - S. K. Jalota; Harsimran Kaur; S. S. Ray; R. Tripathi; Bharat Bhushan Vashisht; S. K. Bal (Regional Environmental Change, 2012)

Acaricide resistance status in Indian isolates of Hyalomma anatolicum - K. P. Shyma; Sachin Kumar; Anil Kumar Sharma; D. D. Ray; S. Ghosh (Experimental and Applied Acarology, 2012)

Unsupervised and supervised classification of hyperspectral imaging data using projection pursuit and Markov random field segmentation - A. Sarkar; A. Vulimiri; S. Paul; Jawaid Iqbal; A. Banerjee; R. Chatterjee; S. S. Ray (International Journal of Remote Sensing, 2012)

Crop Residue Discrimination Using Ground-Based Hyperspectral Data - Rimjhim Bhatnagar Singh; S. S. Ray; S. K. Bal; B. S. Sekhon; G. S. Gill; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2012)

Damage Mechanics of Porcine Flexor Tendon: Mechanical Evaluation and Modeling - Sarah Duenwald-Kuehl; Jaclyn Kondratko; Roderic S. Lakes; Ray Vanderby (Annals of Biomedical Engineering, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Optimization of Culture Conditions for Production of Protease by Two Bacterial Strains, Bacillus licheniformis BF2 and Bacillus subtilis BH4 Isolated from the Digestive Tract of Bata, Labeo bata (Hamilton) - A. K. Ray; S. Mondal; T. Roy (Proceedings of the Zoological Society, 2012)

Sulphide production and corrosion in seawaters during exposure to FAME diesel - Jason S. Lee; Richard I. Ray; Brenda J. Little; Kathleen E. Duncan; Athenia L. Oldham; Irene A. Davidova; Joseph M. Suflita (Biofouling, 2012)

Water Dynamics in Fresh and Frozen Yeasted Dough - Simon M. Loveday; Victor T. Huang; David S. Reid; Ray J. Winger (Critical Reviews in Food Science and Nutrition, 2012)

Particle Size Distribution of Ambient Aerosols in an Industrial Area - B. Padma Rao; A. Srivastava; F. Yasmin; S. Ray; N. Gupta; C. Chauhan; C. V. C. Rao; S. R. Wate (Bulletin of Environmental Contamination and Toxicology, 2012)

Rice Blast Management Through Host-Plant Resistance: Retrospect and Prospects - T. R. Sharma; A. K. Rai; S. K. Gupta; J. Vijayan; B. N. Devanna; S. Ray (Agricultural Research, 2012)

Comparing the benefits of screening for breast cancer and lung cancer using a novel natural history model - Ray S. Lin; Sylvia K. Plevritis (Cancer Causes & Control, 2012)

Comparison of Two Data Smoothing Techniques for Vegetation Spectra Derived From EO-1 Hyperion - Anshu Miglani; Shibendu S. Ray; D. P. Vashishta; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

Correlation of Trace Elemental Profiles in Blood Samples of Indian Patients with Leukoplakia and Oral Submucous Fibrosis - J. G. Ray; Ranjan Ghosh; Debarati Mallick; Niharika Swain; Premdeep Gandhi; S. S. Ram; S. Selvaraj; A. Rathore; Sudarshan Mathummal; Anindita Chakraborty (Biological Trace Element Research, 2011)

A Spatial Database of Cropping System and its Characteristics to Aid Climate Change Impact Assessment Studies - Sushma Panigrahy; Shibendu Shankar Ray; K. R. Manjunath; P. S. Pandey; S. K. Sharma; Anil Sood; Manoj Yadav; P. C. Gupta; N. Kundu; Jai Singh Parihar (Journal of the Indian Society of Remote Sensing, 2011)

VEGF-C differentially regulates VEGF-A expression in ocular and cancer cells; promotes angiogenesis via RhoA mediated pathway - Bharat Kumar; Shailaja A. Chile; Kriti B. Ray; G. E. C. Vidyadhar Reddy; Murali K. Addepalli; A. S. Manoj Kumar; Venkata Ramana; Vikram Rajagopal (Angiogenesis, 2011)

Utility of Hyperspectral Data for Potato Late Blight Disease Detection - Shibendu Shankar Ray; Namrata Jain; R. K. Arora; S. Chavan; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2011)

Stress-adapted extremophiles provide energy without interference with food production - Ray A. Bressan; Muppala P. Reddy; Suk Ho Chung; Dae Jin Yun; Lowell S. Hardin; Hans J. Bohnert (Food Security, 2011)

Microtextural and mineral chemical analyses of andesite–dacite from Barren and Narcondam islands: Evidences for magma mixing and petrological implications - DWIJESH RAY; S RAJAN; RASIK RAVINDRA; ASHIM JANA (Journal of Earth System Science, 2011)

Bromus catharticus striate mosaic virus: a new mastrevirus infecting Bromus catharticus from Australia - James Hadfield; Darren P. Martin; Daisy Stainton; Simona Kraberger; Betty E. Owor; Dionne N. Shepherd; Francisco Lakay; Peter G. Markham; Ray S. Greber; Rob W. Briddon; Arvind Varsani (Archives of Virology, 2011)

Determination of the Relative and Absolute Configurations of the Female-produced Sex Pheromone of the Cerambycid Beetle Prionus californicus - Joshua Rodstein; Jocelyn G. Millar; James D. Barbour; J. Steven McElfresh; Ian M. Wright; Karen S. Barbour; Ann M. Ray; Lawrence M. Hanks (Journal of Chemical Ecology, 2011)

Cold-induced mortality of invasive Burmese pythons in south Florida - Frank J. Mazzotti; Michael S. Cherkiss; Kristen M. Hart; Ray W. Snow; Michael R. Rochford; Michael E. Dorcas; Robert N. Reed (Biological Invasions, 2011)

Mapping of Cropping System for the Indo-Gangetic Plain Using Multi-Date SPOT NDVI-VGT Data - Sushma Panigrahy; Gargi Upadhyay; Shibendu Shankar Ray; Jai S. Parihar (Journal of the Indian Society of Remote Sensing, 2010)

Major ash eruptions of Barren Island volcano (Andaman Sea) during the past 72 kyr: clues from a sediment core record - Neeraj Awasthi; Jyotiranjan S. Ray; Amzad H. Laskar; Alok Kumar; M. Sudhakar; Rajneesh Bhutani; Hetu C. Sheth; Madhusudan G. Yadava (Bulletin of Volcanology, 2010)

Level of Heavy Metals in Some Edible Marine Fishes of Mangrove Dominated Tropical Estuarine Areas of Hooghly River, North East Coast of Bay of Bengal, India - T. K. De; M. De; S. Das; R. Ray; P. B. Ghosh (Bulletin of Environmental Contamination and Toxicology, 2010)

Feasibility Evaluation of Pressurized Irrigation in Canal Commands - Ramesh C. Srivastava; Sheelabhadra Mohanty; Ramlal B. Singandhuppe; Rajiv K. Mohanty; Madhu S. Behera; Lala I. P. Ray; Deepika Sahoo (Water Resources Management, 2010)

Peptides representing the specific variable regions but not the full porin proteins can be useful for antibody based diagnosis of typhoid fever - S. Kumar; S. Kapil; V. Gautam; S. K. Verma; P. Ray (Folia Microbiologica, 2010)

A novel species of mastrevirus (family Geminiviridae) isolated from Digitaria didactyla grass from Australia - Rob W. Briddon; Darren P. Martin; Betty E. Owor; Lara Donaldson; Peter G. Markham; Ray S. Greber; Arvind Varsani (Archives of Virology, 2010)

Assessment of the Jason-2 Extension to the TOPEX/Poseidon, Jason-1 Sea-Surface Height Time Series for Global Mean Sea Level Monitoring - B. D. Beckley; N. P. Zelensky; S. A. Holmes; F. G. Lemoine; R. D. Ray; G. T. Mitchum; S. D. Desai; S. T. Brown (Marine Geodesy, 2010)

An assessment of alternative diesel fuels: microbiological contamination and corrosion under storage conditions - Jason S. Lee; Richard I. Ray; Brenda J. Little (Biofouling, 2010)

Are functional deficits in concussed individuals consistent with white matter structural alterations: combined FMRI & DTI study - K. Zhang; B. Johnson; D. Pennell; W. Ray; W. Sebastianelli; S. Slobounov (Experimental Brain Research, 2010)

Evaluation of plasma hormone concentrations using Enzyme-Immunoassay/Enzyme-linked Immunosorbent assay in healthy Indian men: Effect of ethnicity - M. Sachidhanandam; S. N. Singh; A. K. Salhan; Uday Sankar Ray (Indian Journal of Clinical Biochemistry, 2010)

Carbon and oxygen isotopic compositions of Newania Dolomite Carbonatites, Rajasthan, India: implications for source of carbonatites - Jyotiranjan S. Ray; Anil D. Shukla; Lokesh K. Dewangan (Mineralogy and Petrology, 2010)

Use of preserved museum fish to evaluate historical and current mercury contamination in fish from two rivers in Oklahoma, USA - J. Jaron Hill; Matthew M. Chumchal; Ray W. Drenner; John E. Pinder; S. Matthew Drenner (Environmental Monitoring and Assessment, 2010)

Growth patterns of fossil vertebrates as deduced from bone microstructure: case studies from India - S. Ray; D. Mukherjee; S. Bandyopadhyay (Journal of Biosciences, 2009)

Volcanology and eruptive styles of Barren Island: an active mafic stratovolcano in the Andaman Sea, NE Indian Ocean - Hetu C. Sheth; Jyotiranjan S. Ray; Rajneesh Bhutani; Alok Kumar; R. S. Smitha (Bulletin of Volcanology, 2009)

Crustacean zooplankton community structure in temporary and permanent grassland ponds - S. Matthew Drenner; Stanley I. Dodson; Ray W. Drenner; John E. Pinder III (Hydrobiologia, 2009)

Impact of cropping pattern changes on the exploitation of water resources: A remote sensing and GIS approach - Anil Sood; B. U. Choudhury; S. S. Ray; S. K. Jalota; P. K. Sharma; Shushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2009)

Geology and geochemistry of Pachmarhi dykes and sills, Satpura Gondwana Basin, central India: problems of dyke-sill-flow correlations in the Deccan Traps - Hetu C. Sheth; Jyotiranjan S. Ray; Ranjini Ray; Loÿc Vanderkluysen; John J. Mahoney; Alok Kumar; Anil D. Shukla; Partha Das; Subhrashis Adhikari; Bikashkali Jana (Contributions to Mineralogy and Petrology, 2009)

Antioxidant and redox status after maximal aerobic exercise at high altitude in acclimatized lowlanders and native highlanders - Sanchari Sinha; U. S. Ray; M. Saha; S. N. Singh; O. S. Tomar (European Journal of Applied Physiology, 2009)

Hippuric acid and benzoic acid inhibition of urine derived N 2 O emissions from soil - JANET E. BERTRAM; TIM J. CLOUGH; ROBERT R. SHERLOCK; LEO M. CONDRON; MAUREEN O'CALLAGHAN; NAOMI S. WELLS; JESSICA L. RAY (Global Change Biology, 2009)
Atmospheric concentrations of the greenhouse gas nitrous oxide (N 2 O) have continued to rise since the advent of the industrial era, largely because of the increase in agricultural land use. The urine deposited by grazing ruminant animals is a major global source of agricultural N 2 O. With the first commitment period for reducing greenhouse gas emissions under the Kyoto Protocol now underway, mitigation options for ruminant urine N 2 O emissions are urgently needed. Recent studies showed that increasing the urinary concentration of the minor urine constituent hippuric acid resulted in reduced emissions of N 2 O from a sandy soil treated with synthetic bovine urine, due to a reduction in denitrification. A similar effect was seen when benzoic acid, a product of hippuric acid hydrolysis, was used. This current laboratory experiment aimed to investigate these effects using real cow urine for the first time. Increased concentrations of hippuric acid or benzoic acid in the urine led to reduction of N 2 O emissions by 65% (from 17% to 2 O fluxes. This study indicates the potential for developing a novel mitigation strategy based on manipulation of urine composition through ruminant diet.

Application of manure to no-till soils: phosphorus losses by sub-surface and surface pathways - Peter J. A. Kleinman; Andrew N. Sharpley; Lou S. Saporito; Anthony R. Buda; Ray B. Bryant (Nutrient Cycling in Agroecosystems, 2009)

Adaptive response of equine intestinal Na+/glucose co-transporter (SGLT1) to an increase in dietary soluble carbohydrate - Jane Dyer; Miran Al-Rammahi; Louise Waterfall; Kieron S. H. Salmon; Ray J. Geor; Ludovic Bouré; G. Barrie Edwards; Christopher J. Proudman; Soraya P. Shirazi-Beechey (Pflügers Archiv - European Journal of Physiology, 2009)

Study on the utility of IRS-P6 AWiFS SWIR band for crop discrimination and classification - Rabindra K. Panigrahy; S. S. Ray; S. Panigrahy (Journal of the Indian Society of Remote Sensing, 2009)

Goodenough Spring, Texas, USA: Discharge and water chemistry of a large spring deeply submerged under the binational Amistad Reservoir - Ray H. Kamps; Gregg S. Tatum; Mike Gault; Alan W. Groeger (Hydrogeology Journal, 2009)

Viscoelastic Relaxation and Recovery of Tendon - Sarah E. Duenwald; Ray Vanderby; Roderic S. Lakes (Annals of Biomedical Engineering, 2009)

Evaluation of test results of microbiology laboratories of North India for standard tests for syphilis under an external quality assurance scheme - S. M. Gupta; M. Bala; S. Muralidhar; K. Ray (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Elevated air temperature alters an old‐field insect community in a multifactor climate change experiment - SHAWN N. VILLALPANDO; RAY S. WILLIAMS; RICHARD J. NORBY (Global Change Biology, 2009)
To address how multiple, interacting climate drivers may affect plant–insect community associations, we sampled insects that naturally colonized a constructed old‐field plant community grown for over 2 years under simultaneous CO 2 , temperature, and water manipulation. Insects were sampled using a combination of sticky traps and vacuum sampling, identified to morphospecies and the insect community with respect to abundance, richness, and evenness quantified. Individuals were assigned to four broad feeding guilds in order to examine potential trophic level effects. Although there were occasional effects of CO 2 and water treatment, the effects of warming on the insect community were large and consistent. Warming significantly increased Order Thysanoptera abundance and reduced overall morphospecies richness and evenness. Nonmetric multidimensional scaling found that only temperature affected insect community composition, while a Sørensen similarity index showed less correspondence in the insect community between temperature treatments compared with CO 2 or soil water treatments. Within the herbivore guild, elevated temperature significantly reduced richness and evenness. Corresponding reductions of diversity measures at higher trophic levels (i.e. parasitoids), along with the finding that herbivore richness was a significant predictor of parasitoid richness, suggest trophic‐level effects within the insect community. When the most abundant species were considered in temperature treatments, a small number of species increased in abundance at elevated temperature, while others declined compared with ambient temperature. Effects of temperature in the dominant insects demonstrated that treatment effects were limited to a relatively small number of morphospecies. Observed effects of elevated CO 2 concentration on whole‐community foliar N concentration did not result in any effect on herbivores, which are probably the most susceptible guild to changes in plant nutritional quality. These results demonstrate that climatic warming may alter certain insect communities via effects on insect species most responsive to a higher temperature, contributing to a change in community structure.

Carbon isotopic variations in fluid‐deposited graphite: evidence for multicomponent Rayleigh isotopic fractionation - Jyotiranjan S. Ray (International Geology Review, 2009)

Mitigating Climate Change with Managed Forests: Balancing Expectations, Opportunity, and Risk - David G. Ray; Robert S. Seymour; Neal A. Scott; William S. Keeton (Journal of Forestry, 2009)

Biocontrol Efficacy of Bacillus subtilis Strains Isolated from Cow Dung Against Postharvest Yam (Dioscorea rotundata L.) Pathogens - M. R. Swain; R. C. Ray; C. S. Nautiyal (Current Microbiology, 2008)

Study of the potential of alternative crops by integration of multisource data using a neuro‐fuzzy technique - Anjan Sarkar; Arka Majumdar; Shaunak Chatterjee; Debapriya Chatterjee; Shibendu S. Ray; B. Kartikeyan (International Journal of Remote Sensing, 2008)

Evaluation of EO-1 hyperion data for agricultural applications - Anshu Miglani; S. S. Ray; R. Pandey; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Influence of neotectonic activity on groundwater salinity and playa development in the Mendha river catchment, western India - V. S. Rathore; M. S. Nathawat; P. K. Champati Ray (International Journal of Remote Sensing, 2008)

Sex hormone binding globulin in breast cancer - Dayalu Naik S L; Suresh Hedau; Anil Kumar Bahadur; Renuka Saha; Sudershan Kaur; Amitabha Ray (Indian Journal of Clinical Biochemistry, 2008)

Effect of timing of fungicide application on the development of Fusarium head blight and the accumulation of deoxynivalenol (DON) in winter wheat grain - S. Pirgozliev; R. Ray; S. Edwards; M. Hare; P. Jenkinson (Cereal Research Communications, 2008)

Characterization of the complete genome of influenza A (H5N1) virus isolated during the 2006 outbreak in poultry in India - Koninika Ray; Varsha A. Potdar; Sarah S. Cherian; Shailesh D. Pawar; Santosh M. Jadhav; Shamal R. Waregaonkar; Anshu A. Joshi; Akhilesh C. Mishra (Virus Genes, 2008)

Derivation of crop phenological parameters using multi-date SPOT-VGT-NDVI data: A case study for Punjab - Gargi Upadhyay; S. S. Ray; Sushma Panigrahy (Journal of the Indian Society of Remote Sensing, 2008)

Pharmacodynamic and pharmacokinetic characterisation of RBx 7796: a novel 5-lipoxygenase inhibitor - R. K. Shirumalla; P. Sharma; S. G. Dastidar; J. K. Paliwal; S. Kakar; B. Varshney; G. Singh Saini; V. Sattigeri; M. Salman; A. Ray (Inflammation Research, 2008)

In Vitro Characterization of a Compliant Biodegradable Scaffold with a Novel Bioreactor System - Antonio R. Webb; Bryan D. Macrie; Ananda S. Ray; Jack E. Russo; Andrew M. Siegel; Matthew R. Glucksberg; Guillermo A. Ameer (Annals of Biomedical Engineering, 2007)

Using Generic Pheromone Lures to Expedite Identification of Aggregation Pheromones for the Cerambycid Beetles Xylotrechus nauticus, Phymatodes lecontei, and Neoclytus modestus modestus - Lawrence M. Hanks; Jocelyn G. Millar; Jardel A. Moreira; James D. Barbour; Emerson S. Lacey; J. Steven McElfresh; F. Ray Reuter; Ann M. Ray (Journal of Chemical Ecology, 2007)

The role of medial prefrontal cortex in context-specific inhibition during reversal learning of a visual discrimination - R. J. McDonald; N. Foong; C. Ray; Z. Rizos; N. S. Hong (Experimental Brain Research, 2007)

Calling Behavior of the Cerambycid Beetle Neoclytus acuminatus acuminatus (F.) - Emerson S. Lacey; Ann M. Ray; Lawrence M. Hanks (Journal of Insect Behavior, 2007)

Polymerase Chain Reaction (PCR) Amplification of IS6110 Sequences to detect Mycobacterium tuberculosis Complex from Formalin-fixed Paraffin-embedded Tissues of Deer (Axis axis) - S. Sharma; G. P. Mallick; Rishendra Verma; S. K. Ray (Veterinary Research Communications, 2007)

Mapping of fault rupture of the 28 may 2004 iran earthquake (mw= 6.2) using satellite image - M. Sharifikia; C. S. Dubey; B. K. Sharma; M. Chaudhry; P. K. Champati Ray (Journal of the Indian Society of Remote Sensing, 2006)

RBx 7796: A novel inhibitor of 5-lipoxygenase - R. K. Shirumalla; K. S. Naruganahalli; S. G. Dastidar; V. Sattigeri; G. Kaur; C. Deb; J. B. Gupta; M. Salman; A. Ray (Inflammation Research, 2006)

Predicted taxonomic patterns in pheromone production by longhorned beetles - Ann M. Ray; Emerson S. Lacey; Lawrence M. Hanks (The Science of Nature, 2006)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

RETRACTED ARTICLE: Transgenic rice expressing Allium sativum leaf lectin with enhanced resistance against sap-sucking insect pests - Prasenjit Saha; Pralay Majumder; Indrajit Dutta; Tui Ray; S. C. Roy; Sampa Das (Planta, 2006)

Acetylcholinesterase activities in marine snail (Cronia contracta) as a biomarker of neurotoxic contaminants along the Goa coast, West coast of India - D. Gaitonde; A. Sarkar; S. Kaisary; C. D. Silva; C. Dias; D. P. Rao; D. Ray; R. Nagarajan; S. N. De Sousa; Subhodeep Sarker; D. Patill (Ecotoxicology, 2006)

Effect of ascorbic acid on prevention of hypercholesterolemia induced atherosclerosis - S. Das; R. Ray; Snehlata; N. Das; L. M. Srivastava (Molecular and Cellular Biochemistry, 2006)

Estimating Population Size in a Continuous-time Removal Experiment with a Known Sub-population Size Ratio - Liqun Xi; Paul S. F. Yip; Ray Watson (Environmental and Ecological Statistics, 2006)

Age of the Vindhyan Supergroup: A review of recent findings - Jyotiranjan S Ray (Journal of Earth System Science, 2006)

Preface - Jyotiranjan S Ray; C Chakraborty (Journal of Earth System Science, 2006)

Inhibition of Amazon Deforestation and Fire by Parks and Indigenous Lands - D. NEPSTAD; S. SCHWARTZMAN; B. BAMBERGER; M. SANTILLI; D. RAY; P. SCHLESINGER; P. LEFEBVRE; A. ALENCAR; E. PRINZ; GREG FISKE; ALICIA ROLLA (Conservation Biology, 2006)
Conservation scientists generally agree that many types of protected areas will be needed to protect tropical forests. But little is known of the comparative performance of inhabited and uninhabited reserves in slowing the most extreme form of forest disturbance: conversion to agriculture. We used satellite‐based maps of land cover and fire occurrence in the Brazilian Amazon to compare the performance of large (>10,000 ha) uninhabited (parks) and inhabited (indigenous lands, extractive reserves, and national forests) reserves. Reserves significantly reduced both deforestation and fire. Deforestation was 1.7 (extractive reserves) to 20 (parks) times higher along the outside versus the inside of the reserve perimeters and fire occurrence was 4 (indigenous lands) to 9 (national forests) times higher. No strong difference in the inhibition of deforestation (p= 0.11) or fire (p= 0.34) was found between parks and indigenous lands. However, uninhabited reserves tended to be located away from areas of high deforestation and burning rates. In contrast, indigenous lands were often created in response to frontier expansion, and many prevented deforestation completely despite high rates of deforestation along their boundaries. The inhibitory effect of indigenous lands on deforestation was strong after centuries of contact with the national society and was not correlated with indigenous population density. Indigenous lands occupy one‐fifth of the Brazilian Amazon—five times the area under protection in parks—and are currently the most important barrier to Amazon deforestation. As the protected‐area network expands from 36% to 41% of the Brazilian Amazon over the coming years, the greatest challenge will be successful reserve implementation in high‐risk areas of frontier expansion as indigenous lands are strengthened. This success will depend on a broad base of political support.

Derivation of indices using remote sensing data to evaluate cropping systems - S. S. Ray; Anil Sood; Sushma Panigrahy; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2005)

Sensitization of prostate carcinoma cells to Apo2L/TRAIL by a Bcl-2 family protein inhibitor - S. Ray; O. Bucur; A. Almasan (Apoptosis, 2005)

Molecular pathogenesis of Wilson disease: haplotype analysis, detection of prevalent mutations and genotype–phenotype correlation in Indian patients - A. Gupta; D. Aikath; R. Neogi; S. Datta; K. Basu; B. Maity; R. Trivedi; J. Ray; S. K. Das; P. K. Gangopadhyay; K. Ray (Human Genetics, 2005)

Least cost SO2 emission minimization for a petroleum refinery by optimum use of source reduction, tail gas treatment and flue gas desulphurization - A. K. Dikshit; Amit Dutta; S. Ray (Clean Technologies and Environmental Policy, 2005)

Decreased apoptosis in polyamine depleted IEC-6 cells depends on Akt-mediated NF-κB activation but not GSK3β activity - S. Bhattacharya; R. M. Ray; L. R. Johnson (Apoptosis, 2005)

Reduction of Theileria annulata Infection in Ticks Fed on Calves Immunized with Purified Larval Antigens of Hyalomma anatolicum anatolicum - G. Das; S. Ghosh; D. D. Ray (Tropical Animal Health and Production, 2005)

Use of GIS and remote sensing for crop diversification — a case study for Punjab state - S. S. Ray; Anil Sood; Gargi Das; Sushma Panigrahy; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2005)

Functional and compositional comparison of two activated sludge communities remediating coking effluent - Mike Manefield; Robert I. Griffiths; Mary Beth Leigh; Ray Fisher; Andrew S. Whiteley (Environmental Microbiology, 2005)
Summary The success of engineered microbiological systems is evident in the global application of activated sludge communities to remediate coking effluent. However, there is a lack of understanding of the microbiology underlying treatment efficiency and stability. In this study, two functionally distinct activated sludge pools, treating the same effluent and operating under the same conditions, were examined to establish a relationship between overall diversity and/or functional diversity with respect to process stability. Molecular profiling, sequencing and RNA‐based stable isotope probing were used to examine the bacterial diversity, general composition and functional composition of the most abundant members of the two communities. The inferior process stability in one of the pools could not be explained by reduced total bacterial diversity or evenness. RNA‐based stable isotope probing revealed that both pools harboured an abundant phenol‐degrading Acidovorax species, and that the pool of inferior stability accommodated an additional closely related phenol‐degrading Acidovorax species at high abundance. These results are discussed in the context of deterministic and stochastic models of microbial community assembly.

In Vitro and Pharmacophore-Based Discovery of Novel hPEPT1 Inhibitors - Sean Ekins; Jeffrey S. Johnston; Praveen Bahadduri; Vanessa M. D’Souza; Abhijit Ray; Cheng Chang; Peter W. Swaan (Pharmaceutical Research, 2005)

Water quality assessment of Gautami — Godavari mangrove estuarine ecosystem of Andhra Pradesh, India during September 2001 - S. C. Tripathy; A. K. Ray; S. Patra; V. V. Sarma (Journal of Earth System Science, 2005)

Geodetic sensitivity to surface meteorological data: 24-h and 6-h observing sessions - J. Ray; M. Morrison; S. Hilla; W. Dillinger; G. Mader (GPS Solutions, 2005)

Intra-specific DNA polymorphism in pineapple (Ananas comosus (L.) Merr.) assessed by AFLP markers - Cecilia Y. Kato; Chifumi Nagai; Paul H. Moore; Francis Zee; Minna S. Kim; Denise L. Steiger; Ray Ming (Genetic Resources and Crop Evolution, 2005)

Trace element geochemistry of Amba Dongar carbonatite complex, India: Evidence for fractional crystallization and silicate-carbonate melt immiscibility - Jyotiranjan S. Ray; P. N. Shukla (Journal of Earth System Science, 2004)

Population-based diallel analyses among nine historically recognized alfalfa germplasms - A. Segovia-Lerma; L. W. Murray; M. S. Townsend; I. M. Ray (Theoretical and Applied Genetics, 2004)

Analysis of cropping pattern changes in Bathinda district, Punjab - Sushma Panigrahy; S. S. Ray; Anil Sood; L. B. Patel; P. K. Sharma; J. S. Parihar (Journal of the Indian Society of Remote Sensing, 2004)

Nonlinear Viscoelasticity in Rabbit Medial Collateral Ligament - Rittu V. Hingorani; Paolo P. Provenzano; Roderic S. Lakes; Anthony Escarcega; Ray Vanderby (Annals of Biomedical Engineering, 2004)

Growth, physiology, and chemistry of mycorrhizal and nonmycorrhizalTypha latifolia seedlings - Ryan M. Dunham; Andrew M. Ray; Richard S. Inouye (Wetlands, 2003)

Spatial and Temporal Disturbance Characteristics of Oak-Dominated Old-Growth Stands in the Central Hardwood Forest Region - James S. Rentch; Mary Ann Fajvan; Ray R. Hicks (Forest Science, 2003)
Using a radial growth averaging technique, decadal-scale growth changes of 150- to 350-yr-old overstory oaks were used to identify canopy disturbance events in five old-growth stands, and canopy disturbance intervals were estimated using frequency analysis. Stem maps and tree-establishment and canopy-accession chronologies were then used to reconstruct the size of canopy openings. Between 1700 and 1990, median canopy disturbance interval was approximately 3 yr for each stand; larger disturbances involving two or more trees occurred about every 16 yr per stand. Based on age distribution of the oldest cohorts, three stands became established after a major disturbance, but the majority of multiple-tree disturbances were associated with gaps < 200 m2 in area. Historic disturbance frequency and size distribution of canopy gaps suggest that the oak components of these stands persisted by utilizing a variety of growth strategies appropriate to large and small openings. The absence of significant changes in overstory disturbance frequencies further suggests that increases in the level of understory competition are responsible for the present-day decline in oak dominance.

Development of gypsy moth larvae feeding on red maple saplings at elevated CO 2 and temperature - Ray S. Williams; David E. Lincoln; Richard J. Norby (Oecologia, 2003)

Co-expression of a Modified Maize Ribosome-inactivating Protein and a Rice Basic Chitinase Gene in Transgenic Rice Plants Confers Enhanced Resistance to Sheath Blight - Ju-Kon Kim; In-Cheol Jang; Ray Wu; Wei-Neng Zuo; Rebecca S. Boston; Yong-Hwan Lee; Il-Pyung Ahn; Baek Hie Nahm (Transgenic Research, 2003)

DDT and HCH Residues in Basmati Rice (Oryza sativa) Cultivated in Dehradun (India) - G. Suresh Babu; M. Farooq; R. S. Ray; P. C. Joshi; P. N. Viswanathan; R. K. Hans (Water, Air, & Soil Pollution, 2003)

Avenues for increasing salt tolerance of crops, and the role of physiologically based selection traits - Rana Munns; Shazia Husain; Anna Rita Rivelli; Richard A. James; A.G. Condon; Megan P. Lindsay; Evans S. Lagudah; Daniel P. Schachtman; Ray A. Hare (Plant and Soil, 2002)

Productivity optimisation in weak sedimentary formations for improved coal production and roof stability—an approach - V. M. S. R. Murthy; Santosh Kumar Ray (Geotechnical and Geological Engineering, 2002)

Short-arc analysis of intersatellite tracking data in a gravity mapping mission - D. D. Rowlands; R. D. Ray; D. S. Chinn; F. G. Lemoine (Journal of Geodesy, 2002)

Effect of young age on prostate cancer survival: a population-based assessment (United States) - Ray M. Merrill; Justin S. Bird (Cancer Causes & Control, 2002)

Environmental impact assessment and its minimisation in a refinery using life cycle impact analysis approach - Amit Dutta; A. K. Dikshit; S. Ray; M. Bandyopadhyay (The International Journal of Life Cycle Assessment, 2002)

Strategies for carbon acquisition in the red marine macroalga Coccotylus truncatus from the Baltic Sea - Snoeijs P.; Klenell M.; Choo K.; Comhaire I.; Ray S.; Pedersén M. (Marine Biology, 2002)

Using GIS for siting artificial reefs—Data issues, problems and solutions: ‘Real World’ to ‘Real World’ - D. R. Green; S. T. Ray (Journal of Coastal Conservation, 2002)

Protein A-activated macrophages induce apoptosis in Ehrlich's ascites carcinoma through a nitric oxide-dependent pathway - S. Chattopadhyay; T. Das; G. Sa; P. K. Ray (Apoptosis, 2002)

Non-litter effects of elevated CO2 on forest floor microarthropod abundances - Randi A. Hansen; Ray S. Williams; David C. Degenhardt; David E. Lincoln (Plant and Soil, 2001)

40Ar-39Ar age of carbonatite-alkaline magmatism in Sung valley, Meghalaya, India - Jyotiranjan S Ray; Kanchan Pande (Journal of Earth System Science, 2001)

Tracing the Sources of Exported Nitrate in the Turkey Lakes Watershed Using 15 N/ 14 N and 18 O/ 16 O isotopic ratios - John Spoelstra; Sherry L. Schiff; Richard J. Elgood; Ray G. Semkin; Dean S. Jeffries (Ecosystems, 2001)

Trends in the Output of First-order Basins at Turkey Lakes Watershed, 1982-96 - Fredrick D. Beall; Ray G. Semkin; Dean S. Jeffries (Ecosystems, 2001)

Serum oestradiol in women with carcinomas of the breast and uterine cervix - Amitabha Ray; Anil Kumar Bahadur; S. L. Dayalu Naik; Bhuvnesh Kumar Sharma (Indian Journal of Clinical Biochemistry, 2001)

High iridium concentration of alkaline rocks of Deccan and implications to K/T boundary - P. N. Shukla; N. Bhandari; Anirban Das; A. D. Shukla; J. S. Ray (Journal of Earth System Science, 2001)

Identification and classification of aromatic rices based on DNA fingerprinting - P. Ray Choudhury; S. Kohli; K. Srinivasan; T. Mohapatra; R.P. Sharma (Euphytica, 2001)

Integrated commodity management methods with ca and/or fumigation - S. Prabhakaran; S. Ray; B. M. Schneider; R. E. Williams; P. Flinn; T. Phillips; D. Hagstrum; F. Arthur; J. Throne; R. N. Emery; R. A. Tassone; E. Kostas; et al. (Phytoparasitica, 2001)

Serum lipids, lipoproteins and sex-hormone binding globulin in breast cancer - A. Ray; S. L. Dayalu Naik; A. K. Bahadur; S. T. Pasha; R. S. Rautela; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Status of epidermal growth factor receptors family in hormone-dependent carcinomas of the breast and prostate with reference to serum lipids and lipoproteins - D. Jain; A. Ray; A. K. Bahadur; K. U. Chaturvedi; R. Sood; S. Sharma; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2001)

Recent Improvements to IERS Bulletin A Combination and Prediction - Brian J. Luzum; Jim R. Ray; Merri S. Carter; F. Jerry Josties (GPS Solutions, 2001)

Land Use/Land Cover Change Mapping In Mahi Canal Command Area, Gujarat, Using Multi-temporal Satellite Data - V. S. Brahmabhatt; G. B. Dalwadi; S. B. Chhabra; S. S. Ray; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2000)

Early effects of hypoxia/reoxygenation on VEGF, Ang-1, Ang-2 and their receptors in the rat myocardium: Implications for myocardial angiogenesis - Parth S. Ray; Tatiana Estrada-Hernandez; Hiroaki Sasaki; Li Zhu; Nilanjana Maulik (Molecular and Cellular Biochemistry, 2000)

Frequency of cytochrome P 450 3A4 variant genotype in transplant population and lack of association with cyclosporin clearance - L. P. Rivory; H. Qin; S. J. Clarke; J. Eris; G. Duggin; E. Ray; R. J. Trent; J. F. Bishop (European Journal of Clinical Pharmacology, 2000)

A rare case of two malignancies: Carcinoma of the breast and uterine cervix - A. Ray; H. Mukundan; A. K. Bahadur; R. S. Rautela; S. L. D. Naik; B. K. Sharma (Indian Journal of Clinical Biochemistry, 2000)

Effects of elevated CO 2 and temperature‐grown red and sugar maple on gypsy moth performance - Ray S. Williams; Richard J. Norby; David E. Lincoln (Global Change Biology, 2000)
Summary Few studies have investigated how tree species grown under elevated CO 2 and elevated temperature alter the performance of leaf‐feeding insects. The indirect effects of an elevated CO 2 concentration and temperature on leaf phytochemistry, along with potential direct effects on insect growth and consumption, may independently or interactively affect insects. To investigate this, we bagged larvae of the gypsy moth on leaves of red and sugar maple growing in open‐top chambers in four CO 2 /temperature treatment combinations: (i) ambient temperature, ambient CO 2 ; (ii) ambient temperature, elevated CO 2 (+ 300 μL L −1 CO 2 ); (iii) elevated temperature (+ 3.5°C), ambient CO 2 ; and (iv) elevated temperature, elevated CO 2 . For both tree species, leaves grown at elevated CO 2 concentration were significantly reduced in leaf nitrogen concentration and increased in C: N ratio, while neither temperature nor its interaction with CO 2 concentration had any effect. Depending on the tree species, leaf water content declined (red maple) and carbon‐based phenolics increased (sugar maple) on plants grown in an enriched CO 2 atmosphere. The only observed effect of elevated temperature on leaf phytochemistry was a reduction in leaf water content of sugar maple leaves. Gypsy moth larval responses were dependent on tree species. Larvae feeding on elevated CO 2 ‐grown red maple leaves had reduced growth, while temperature had no effect on the growth or consumption of larvae. No significant effects of either temperature or CO 2 concentration were observed for larvae feeding on sugar maple leaves. Our data demonstrate strong effects of CO 2 enrichment on leaf phytochemical constituents important to folivorous insects, while an elevated temperature largely has little effect. We conclude that alterations in leaf chemistry due to an elevated CO 2 atmosphere are more important in this plant–folivorous insect system than either the direct short‐term effects of temperature on insect performance or its indirect effects on leaf chemistry.

A GIS and remote sensing based approach for siting cold storage infrastructure for horticultural crops: A case study for potato crop in Bardhaman district, West Bengal, India - S S Ray; N Kundu; S Dutta; S Panigrahy (Journal of the Indian Society of Remote Sensing, 2000)

Self-organised criticality in a genetic model of species-species interaction - Tane S. Ray; Leo Moseley; Naeem Jan (Theory in Biosciences, 2000)

Emplacement of Amba Dongar carbonatite-alkaline complex at Cretaceous/Tertiary boundary: Evidence from40Ar-39Ar chronology - Jyotiranjan S. Ray; Kanchan Pande; T. R. Venkatesan (Journal of Earth System Science, 2000)

The modified wave estimator as an alternative to a Kalman filter for real-time GPS/GLONASS-INS integration - J. K. Ray; O. S. Salychev; M. E. Cannon (Journal of Geodesy, 1999)

Antifungal activity of Δ3-alstovenine, a plant alkaloid isolated fromAlstonia venenata - S. K. Singh; B. K. Sarma; J. S. Srivastava; U. P. Singh; A. B. Ray (Folia Microbiologica, 1999)

Reactive oxygen species function as second messenger during ischemic preconditioning of heart - Dipak K. Das; Nilanjana Maulik; Motoaki Sato; Partha S. Ray (Molecular and Cellular Biochemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Movement-related potentials with reference to isometric force output in discrete and repetitive tasks - S. M. Slobounov; William J. Ray (Experimental Brain Research, 1998)

Adaptation to low temperature and regulation of gene expression in antarctic psychrotrophic bacteria - Malay K Ray; G Seshu Kumar; Kamala Janiyani; K Kannan; Pratik Jagtap; Malay K Basu; S Shivaji (Journal of Biosciences, 1998)

Interaction of the non-protein-coding developmental and stress-induciblehsrω gene withRas genes ofDrosophila melanogaster - Pritha Ray; S C Lakhotia (Journal of Biosciences, 1998)

The role of prostate-specific antigen (PSA) testing patterns in the recent prostate cancer incidence declinein the United States - Julie M. Legler; Eric J. Feuer; Arnold L. Potosky; Ray M. Merrill; Barnett S. Kramer (Cancer Causes & Control, 1998)

Cloning and tissue expression of the mouse ortholog of AIM1, a βγ-crystallin superfamily member - Ulrike Teichmann; Michael E. Ray; Jane Ellison; Caroline Graham; Graeme Wistow; Paul S. Meltzer; Jeffrey M. Trent; William J. Pavan (Mammalian Genome, 1998)

Leaf age effects of elevated CO 2 ‐grown white oak leaves on spring‐feeding lepidopterans - RaY. S. Williams; David E. Lincoln; Richard J. Norby (Global Change Biology, 1998)
Folivorous insect responses to elevated CO 2 ‐grown tree species may be complicated by phytochemical changes as leaves age. For example, young expanding leaves in tree species may be less affected by enriched CO 2 ‐alterations in leaf phytochemistry than older mature leaves due to shorter exposure times to elevated CO 2 atmospheres. This, in turn, could result in different effects on early vs. late instar larvae of herbivorous insects. To address this, seedlings of white oak ( Quercus alba L.), grown in open‐top chambers under ambient and elevated CO 2 , were fed to two important early spring feeding herbivores; gypsy moth ( Lymantria dispar L.), and forest tent caterpillar ( Malacosoma disstria Hübner). Young, expanding leaves were presented to early instar larvae, and older fully expanded or mature leaves to late instar larvae. Young leaves had significantly lower leaf nitrogen content and significantly higher total nonstructural carbohydrate:nitrogen ratio as plant CO 2 concentration rose, while nonstructural carbohydrates and total carbon‐based phenolics were unaffected by plant CO 2 treatment. These phytochemical changes contributed to a significant reduction in the growth rate of early instar gypsy moth larvae, while growth rates of forest tent caterpillar were unaffected. The differences in insect responses were attributed to an increase in the nitrogen utilization efficiency (NUE) of early instar forest tent caterpillar larvae feeding on elevated CO 2 ‐grown leaves, while early instar gypsy moth larval NUE remained unchanged among the treatments. Later instar larvae of both insect species experienced larger reductions in foliage quality on elevated CO 2 ‐grown leaves than earlier instars, as the carbohydrate:nitrogen ratio of leaves substantially increased. Despite this, neither insect species exhibited changes in growth or consumption rates between CO 2 treatments in the later instar. An increase in NUE was apparently responsible for offsetting reduced foliar nitrogen for the late instar larvae of both species.

Body composition in air and road inductees at high altitude during the initial days of acclimatization - U. S. Ray; W. Selvamurthy (International Journal of Biometeorology, 1998)

Integrated measures of ambient toxicity and fish community diversity in Chesapeake Bay tributaries - S. Ian Hartwell; Celia E. Dawson; Eric Q. Durell; Ray W. Alden; Peter C. Adolphson; David A. Wright; Gina M. Coelho; John A. Magee (Ecotoxicology, 1998)

Studies on ‘zinc deficiency syndrome’ in Black Bengal goats (Capra hircus) fed with fodder (Andropogon gayanus) grown on soil treated with an excess of calcium and phosphorus fertilizer - S.K. Ray; R. Roychoudhury; S.K. Bandopadhyayi; S. Basu (Veterinary Research Communications, 1997)

Studies on mercury-detoxicating enzymes from a broad-spectrum mercury-resistant strain ofFlavobacterium rigense - R. Gachhui; J. Chaudhuri; S. Ray; K. Pahan; A. Mandal (Folia Microbiologica, 1997)

Spike detection in biomedical signals using midprediction filter - S. Dandapat; G. C. Ray (Medical & Biological Engineering & Computing, 1997)

Susceptibility of potato varieties and advanced breeding lines (Solanum tuberosum L.) toPhytophthora infestans (Mont.) de Bary in greenhouse screenings - David S. Douches; William W. Kirk; Kazimierz Jastrzebski; Christopher Long; Ray Hammerschmidt (American Journal of Potato Research, 1997)

Short‐Term and Small‐Scale Variation in Food Availability to Natural Oyster Populations: Food, Flow and Flux - E. A. Wilson‐Ormond; E. N. Powell; S. M. Ray (Marine Ecology, 1997)
Food resources and water flow speeds vary on short‐temporal and small‐spatial scales important to feeding in natural populations of oysters ( Crassostrea virginica ). To better describe food availability to the oyster population, micro‐current meters were used to measure flow 1–3 cm above the bottom and frequent water sampling was used to determine the quantity and composition of the seston on Confederate Reef, Galveston Bay, Texas. The quantity and quality of food varied on time scales at least as short as 3 h and throughout the water column. Seston was high in detrital carbon, nitrogen poor, and had a high fraction of inorganic particles. The quantity of food at the bed was not predictable from samples taken near the surface. Water flow speeds were also highly variable. Whereas rapid flow speeds were measured, flow speed tended to cluster about a narrower range of slower speeds resulting in the mean speed being much higher than the median. Fluxes of food calculated from the quantity of food and water flow speeds were low and highly variable. Under most conditions, water flow speed was more important than food quantity in determining flux. Rapid flow rates could overcome low food quantity to result in relatively high fluxes, whereas slow flow resulted in small fluxes even if food was abundant. Changes in water flow rate associated with tidal changes and changes in speed are probably the primary agents controlling food availability on a daily basis. Decreased wind speed at night normally reduced flux in the early morning hours, for example. These results stress the importance of measuring food quantity and water flow speed on spatial and temporal scales important to oyster feeding. Model simulations of oyster populations at varying densities, flow rates and clump heights across the range of measured values show that flow rate is insufficient during most hours of the day and days of the year to prevent oysters from locally reducing food supply by their filtering efforts. Thus flow rate probably limits population density and adult size on Confederate Reef.

Nebulization of NanoCrystals™: Production of a Respirable Solid-in-Liquid-in-Air Colloidal Dispersion - Timothy S. Wiedmann; Lan DeCastro; Ray W. Wood (Pharmaceutical Research, 1997)

Effect of a growth hormone treatment on bone orthotropic elasticity in dwarf rats - Sean S. Kohles; Daniel A. Martinez; James R. Bowers; Arthur C. Vailas; Ray Vanderby (Annals of Biomedical Engineering, 1997)

Suppressive effect of quinalphos on the activity of accessory sex glands and plasma concentrations of gonadotrophins and testosterone in rats - A. Ray; S. Chatterjee; S. Ghosh; S. N. Kabir; A. Pakrashi; C. Deb (Archives of Environmental Contamination and Toxicology, 1991)

Effect of methyl isocyanate (MIC) on rat erythrocytes - Deepa Agrawal; G. S. D. Gupta; J. S. Shukla; K. K. Dutta; P. K. Ray (Archives of Toxicology, 1990)

Pleiotropic effect of the gene hairless on hepatotoxicity of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin in mice - J. B. Greig; J. E. Francis; S. J. E. Kay; T. Lister; D. E. Ray; A. A. Seawright; A. G. Smith (Archives of Toxicology, 1987)

Human bactericidal antibody response to meningococcal outer membrane protein vaccines - W. D. Zollinger; J. Boslego; L. O. Frholm; J. S. Ray; E. E. Moran; B. L. Brandt (Antonie van Leeuwenhoek, 1987)

Chemical and biological characterization of volatile components of environmental samples after fractionation by vacuum line cryogenic distillation - Ray L. Hanson; Alan R. Dahl; Simon J. Rothenberg; Janet M. Benson; Antone L. Brooks; John S. Dutcher (Archives of Environmental Contamination and Toxicology, 1985)

Effects of cadmium on yolk utilization, growth, and survival of Atlantic salmon alevins and newly feeding fry - R. H. Peterson; J. L. Metcalfe; S. Ray (Archives of Environmental Contamination and Toxicology, 1983)

Effects of copper on the sabellid polychaete,Eudistylia vancouveri. II. Copper accumulation and tissue injury in the branchial crown - James S. Young; Roy R. Adee; Irene Piscopo; Ray L. Buschbom (Archives of Environmental Contamination and Toxicology, 1981)

Accumulation of cadmium byNereis virens - S. Ray; D. McLeese; D. Pezzack (Archives of Environmental Contamination and Toxicology, 1980)

The disposition of cadmium and zinc inPandalus montagui - S. Ray; D. W. McLeese; B. A. Waiwood; D. Pezzack (Archives of Environmental Contamination and Toxicology, 1980)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Effects of copper on the sabellid polychaete,Eudistylia vancouveri: I. Concentration limits for copper accumulation - James S. Young; Ray L. Buschbom; James M. Gurtisen; Stephen P. Joyce (Archives of Environmental Contamination and Toxicology, 1979)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)